Multilayer container, method for producing the same, and method for producing recycled polyester

By combining the polyester layer and the polyamide layer in a multi-layer container, and adding yellowing inhibitors and oxidation accelerators to the polyamide layer, the problems of yellowing and insufficient oxygen resistance of the regenerated polyester are solved, and efficient Yellowing inhibition and oxygen resistance increase.

CN115243891BActive Publication Date: 2025-02-25MITSUBISHI GAS CHEM CO INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180018924.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-20
Filing Date
2021-02-25
Publication Date
2025-02-25
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

The yellowing of recycled polyester is greatly affected by oxidation, which makes it difficult to improve the oxygen resistance of the container, and it is easy to aggravate the yellowing during the recycling and reuse process, reducing the commodity value of the packaging container.

Method used

The design of a multi-layer container is adopted, including a polyester layer and a polyamide layer, and the yellowing inhibitor and oxidation accelerator are added to the polyamide layer, and prepared by co-injection molding and blow molding processes.

Benefits of technology

It effectively inhibits the yellowing of recycled polyester, improves the oxygen resistance of the container, extends the service life of the container, and improves the quality of recycled polyester after recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003829058530000061
    Figure BDA0003829058530000061
  • Figure BDA0003829058530000071
    Figure BDA0003829058530000071
  • Figure BDA0003829058530000081
    Figure BDA0003829058530000081
Patent Text Reader

Abstract

A multi-layer container comprising: a polyester layer comprising a polyester resin (X); and a polyamide layer comprising a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B), wherein the content of the polyamide resin (Y) is 0.05 to 7.0% by mass relative to the total amount of all polyamide layers and all polyester layers, and the yellowing inhibitor (A) is a dye, and the content of the yellowing inhibitor (A) is 1 to 30 ppm relative to the total amount of all polyamide layers and all polyester layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multi-layer container, a method for producing the same, and a method for producing recycled polyester. Background Art

[0002] Aromatic polyester resins obtained by using aromatic dicarboxylic acid compounds and aliphatic diol compounds as monomers have excellent characteristics such as transparency, mechanical properties, melting stability, solvent resistance, aroma retention, gas barrier properties, and recyclability. Therefore, aromatic polyester resins such as polyethylene terephthalate (PET) are widely used in various packaging materials such as films, sheets, and hollow containers. Polyester resins have high gas barrier properties, but they may not be sufficient for uses that require further gas barrier properties against oxygen, carbon dioxide gas, etc. Therefore, as a means of improving the gas barrier properties of polyester resins, the following operations have been performed: evaporating aluminum oxide and silicon oxide onto molded bodies and packaging containers formed by polyester resins; applying resins with high gas barrier properties to molded bodies and packaging containers formed by polyester resins and laminating, or performing melt mixing.

[0003] As gas barrier resins, polyamide resins such as nylon 6 and nylon 66, and ethylene-vinyl alcohol copolymers can be cited. Among polyamide resins, polyphenylene adipamide obtained by polymerizing a diamine component with benzylene diamine as the main component and a dicarboxylic acid component with adipic acid as the main component has excellent gas barrier properties. Polyphenylene adipamide not only has high gas barrier properties, but also has a glass transition temperature, a melting point, and a crystallinity similar to polyethylene terephthalate, which is a widely used polyester resin, and is therefore easily laminated and melt-mixed into polyester resins. Thus, polyphenylene adipamide is very suitable as a material for improving the gas barrier properties of polyester resins.

[0004] However, the yellowing caused by the thermal history of the polyester resin composition containing polyamide is more likely to be aggravated than that of polyester alone. Therefore, yellowing occurs particularly in the recycling process of recycling containers and reusing resins. This becomes a factor that reduces the commodity value of packaging containers, and therefore, research on suppressing yellowing has been conducted. For example, Patent Document 1 discloses a multilayer container and a method for producing recycled polyester, wherein the multilayer container has: a polyester resin composition layer containing a polyester resin and an amino compound having yellowing suppressing ability, and a polyamide resin layer containing a polyamide resin.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2017 / 057463 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The yellowing of recycled polyester is greatly affected by oxidation. If a raw material that absorbs oxygen is used for the container, the yellowing worsens. Therefore, it is difficult to improve the oxygen barrier property of the container. There is a demand for a container that can achieve both yellowing suppression and high oxygen barrier property.

[0010] Therefore, an object of the present invention is to provide a multilayer container having excellent oxygen barrier properties, a multilayer container capable of suppressing yellowing of recycled polyester during recycling, and a method for producing recycled polyester with suppressed yellowing.

[0011] Solutions for solving problems

[0012] The present inventors have conducted intensive studies in view of the above problems and have found that a multilayer container having a polyester layer and a polyamide layer containing a polyamide resin, a specific yellowing inhibitor, and an oxidation accelerator can solve the above problems, thereby completing the present invention.

[0013] The present invention provides the following [1] to

[25] .

[0014] [1] A multilayer container comprising: a polyester layer comprising a polyester resin (X); and a polyamide layer comprising a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B), wherein the content of the polyamide resin (Y) is 0.05 to 7.0% by mass relative to the total amount of all the polyamide layers and all the polyester layers, and the yellowing inhibitor (A) is a dye, and the content of the yellowing inhibitor (A) is 1 to 30 ppm relative to the total amount of all the polyamide layers and all the polyester layers.

[0015] [2] The multilayer container according to [1] above, wherein the polyester resin (X) comprises structural units derived from dicarboxylic acid and structural units derived from diol, wherein the structural units derived from the dicarboxylic acid contain 80 mol % or more of structural units derived from terephthalic acid, and the structural units derived from the diol contain 80 mol % or more of structural units derived from ethylene glycol.

[0016] [3] The multilayer container according to [1] or [2] above, wherein the polyamide resin (Y) comprises a structural unit derived from a diamine and a structural unit derived from a dicarboxylic acid, wherein the structural unit derived from the diamine contains 80 mol % or more of a structural unit derived from xylenediamine, and the structural unit derived from the dicarboxylic acid contains 80 mol % or more of a structural unit derived from adipic acid.

[0017] [4] The multi-layer container according to any one of [1] to [3] above, wherein the oxidation promoter (B) is a compound containing a transition metal.

[0018] [5] The multilayer container according to [4] above, wherein the transition metal is at least one selected from the group consisting of cobalt, iron, manganese, and nickel.

[0019] [6] The multi-layer container according to any one of [1] to [5] above, wherein the yellowing inhibitor (A) is an anthraquinone-based dye.

[0020] [7] The multilayer container according to any one of [1] to [6] above, wherein the polyamide layer further contains a greening inhibitor (C).

[0021] [8] The multi-layer container according to [7] above, wherein the greening inhibitor (C) is at least one selected from the group consisting of anthraquinone dyes and azo dyes.

[0022] [9] The multilayer container according to any one of [1] to [8] above, wherein the polyamide layer further contains a polyester resin (Z).

[0023]

[10] The multilayer container according to [9] above, wherein the content of the polyester resin (Z) in the polyamide layer is 5 to 70% by mass.

[0024]

[11] The multi-layer container according to any one of [1] to

[10] above, wherein the multi-layer container is a multi-layer hollow container.

[0025]

[12] The multilayer container according to any one of [1] to

[11] above, wherein the multilayer container has a 2-5 layer structure, and the outermost layer is a polyester layer.

[0026]

[13] The multilayer container according to any one of [1] to

[12] above, wherein the multilayer container has a 3-5 layer structure, and the outermost layer and the innermost layer are polyester layers.

[0027]

[14] A method for producing a multilayer container, wherein the multilayer container comprises: a polyester layer comprising a polyester resin (X); and a polyamide layer comprising a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B), wherein the content of the polyamide resin (Y) is 0.05 to 7.0% by mass relative to the total amount of all the polyamide layers and all the polyester layers, and the yellowing inhibitor (A) is a dye, and the content of the yellowing inhibitor (A) is 1 to 30 ppm relative to the total amount of all the polyamide layers and all the polyester layers, the production method comprising the following steps: step 1, mixing the polyamide resin (Y), the yellowing inhibitor (A) and the oxidation accelerator (B) to prepare a polyamide resin mixture; step 2, co-injection molding the polyamide resin mixture and a polyester resin composition comprising the polyester resin (X) to obtain a multilayer preform; and step 3, blow molding the multilayer preform.

[0028]

[15] The method for producing a multi-layer container according to

[14] above, wherein in step 1, a greening inhibitor (C) is further mixed.

[0029]

[16] The method for producing a multi-layer container according to

[14] or

[15] above, wherein in step 1, a polyester resin (Z) is further mixed.

[0030]

[17] A method for producing a multilayer container according to any one of

[14] to

[16] above, wherein in step 1, a polyamide resin or a polyester resin, a yellowing inhibitor (A) and an oxidation accelerator (B) are kneaded and then mixed with a polyamide resin (Y).

[0031]

[18] The method for producing a multi-layer container according to any one of

[14] to

[17] above, wherein the oxidation promoter (B) is a compound containing a transition metal.

[0032]

[19] The method for producing a multi-layer container according to

[18] above, wherein the transition metal is at least one selected from the group consisting of cobalt, iron, manganese, and nickel.

[0033]

[20] The method for producing a multi-layer container according to any one of

[14] to

[19] above, wherein the yellowing inhibitor (A) is an anthraquinone-based dye.

[0034]

[21] The method for producing a multi-layer container according to any one of

[15] to

[20] , wherein the greening inhibitor (C) is at least one selected from the group consisting of anthraquinone dyes and azo dyes.

[0035]

[22] A method for producing regenerated polyester, comprising the step of recovering polyester from the multilayer container according to any one of [1] to

[13] .

[0036]

[23] The method for producing a regenerated polyester according to

[22] , further comprising the step of removing all or part of the polyamide layer from the multilayer container to recover the polyester.

[0037]

[24] The method for producing regenerated polyester according to

[22] or

[23] , wherein after the multi-layer container is pulverized, the polyamide layer is removed by air separation.

[0038]

[25] The method for producing a regenerated polyester according to any one of

[22] to

[24] , wherein after the step of recovering the polyester, one or more steps selected from a crystallization step and a solid phase polymerization step are performed.

[0039] Effects of the Invention

[0040] According to the present invention, it is possible to provide a multilayer container having excellent oxygen barrier properties and capable of suppressing yellowing of recycled polyester during recycling, and a method for producing recycled polyester with suppressed yellowing. DETAILED DESCRIPTION

[0041] [Multi-layer container]

[0042] The multilayer container of the present invention comprises: a polyester layer comprising a polyester resin (X); and a polyamide layer comprising a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B), wherein the content of the polyamide resin (Y) is 0.05 to 7.0% by mass relative to the total amount of all polyamide layers and all polyester layers, and the yellowing inhibitor (A) is a dye, and the content of the yellowing inhibitor (A) is 1 to 30 ppm relative to the total amount of all polyamide layers and all polyester layers.

[0043] The reason why the multi-layer container of the present invention can achieve both oxygen barrier properties and yellowing suppression of the recycled polyester is not particularly limited, but is considered to be as follows.

[0044] The oxygen barrier layer formed by the polyamide resin further helps the oxidation promoter to absorb oxygen, thereby improving the oxygen barrier property. The dye with a stable structure and a small amount of yellowing inhibitor do not hinder the oxidation promotion effect, effectively suppressing the yellowing of the recycled polyester, so it is considered that these can be achieved.

[0045] The “total weight of all polyamide layers and all polyester layers” means the total weight of all polyamide layers and all polyester layers constituting the multilayer container, and when there are multiple layers, it means the total weight of all of them.

[0046] <Polyester layer>

[0047] The polyester layer contains a polyester resin (X).

[0048] (Polyester resin (X))

[0049] The polyester resin (X) contained in the polyester layer is preferably a condensation polymer of dicarboxylic acid and diol, and preferably has a structural unit derived from dicarboxylic acid (dicarboxylic acid unit) and a structural unit derived from diol (diol unit).

[0050] Examples of the dicarboxylic acid unit include a structural unit derived from an aromatic dicarboxylic acid, a structural unit derived from an alicyclic dicarboxylic acid, and a structural unit derived from an aliphatic dicarboxylic acid. A structural unit derived from an aromatic dicarboxylic acid is preferred.

[0051] Examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, biphenyl dicarboxylic acid, diphenyl ether dicarboxylic acid, diphenyl sulfone dicarboxylic acid, diphenyl ketone dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, and 2,7-naphthalene dicarboxylic acid. From the viewpoint of cost and ease of production, terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, and 4,4′-biphenyl dicarboxylic acid are preferred, and terephthalic acid, isophthalic acid, and naphthalene dicarboxylic acid are more preferred. From the viewpoint of moldability, terephthalic acid and isophthalic acid are further preferred, and terephthalic acid is still more preferred.

[0052] As the aromatic dicarboxylic acid, a C1-4 alkyl ester of the aromatic dicarboxylic acid can be used.

[0053] When recycling the multilayer container of the present invention, it may be melt-kneaded with a conventional single-layer container made of a polyester resin. By having a unit derived from terephthalic acid as a dicarboxylic acid unit, the multilayer container of the present invention has good compatibility with conventional single-layer containers, and good recyclability can be obtained.

[0054] As the aromatic dicarboxylic acid, sulfophthalic acid and sulfophthalic acid metal salts can be used. The sulfophthalic acid metal salt is a metal salt of sulfophthalic acid, and examples of the metal atom include alkali metals and alkaline earth metals.

[0055] Specifically, sulfophthalic acid or a metal salt of sulfophthalic acid is represented by the following formula (I) or (I'), respectively.

[0056]

[0057] In the above formula (I'), M is a metal atom and n represents the valence of M.

[0058] Examples of the metal atom of M include alkali metals such as lithium, sodium, and potassium; and alkaline earth metals such as beryllium, magnesium, calcium, and strontium. Among them, alkali metals are preferred, sodium or lithium is preferred, and sodium is more preferred. It should be noted that when n is 2 or more, M can be cross-linked with other units (e.g., other sulfophthalic acid units or sulfo groups in sulfophthalic acid metal salt units).

[0059] In the above formulas (I) and (I'), R A is a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group. m represents an integer of 0 to 3. It should be noted that when m is 2 or 3, each R A Optional same or different.

[0060] Examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-octyl, and 2-ethylhexyl. Among them, an alkyl group having 1 to 6 carbon atoms is preferred, and an alkyl group having 1 to 4 carbon atoms is more preferred.

[0061] Examples of the aryl group include a phenyl group, a naphthyl group, etc. Among them, an aryl group having 6 to 12 carbon atoms is preferred, and a phenyl group is more preferred.

[0062] Examples of the substituents that the above-mentioned alkyl and aryl groups may have include halogen atoms such as chlorine atoms, bromine atoms, and iodine atoms, alkyl groups, alkenyl groups, aryl groups, cyano groups, hydroxyl groups, nitro groups, alkoxy groups, aryloxy groups, acyl groups, amino groups, mercapto groups, alkylthio groups, arylthio groups, etc. Among these groups, when they have hydrogen atoms, they may be further substituted with the above-mentioned substituents.

[0063] As R A Specific examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, 1-methylpropyl, 2-methylpropyl, hydroxymethyl, 1-hydroxyethyl, mercaptomethyl, methylthioethyl, phenyl, naphthyl, biphenyl, benzyl and 4-hydroxybenzyl, among which methyl, ethyl and benzyl are preferred.

[0064] In the above formulas (I) and (I'), R B It represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0065] For the preferred R A As described above, the sulfophthalic acid or sulfophthalic acid metal salt used in the polyester resin (X) preferably has m=0, that is, the benzene ring is not R A The units are substituted with the units represented by the following formula (Ia) or (I'a).

[0066]

[0067] In the above formula (Ia), R B and R in the above formula (I) B same.

[0068] In the above formula (I'a), R B , M and n are the same as R in the above formula (I') B , M and n are the same.

[0069] Furthermore, examples of the sulfophthalic acid represented by the above formula (Ia) or the sulfophthalic acid metal salt represented by the above formula (I'a) include a phthalic acid structure in which two -CO- are bonded to the ortho position, an isophthalic acid structure bonded to the meta position, and a terephthalic acid structure bonded to the para position, among which the isophthalic acid structure is preferred. That is, at least one of the sulfoisophthalic acid represented by the following formula (Ib) and the sulfoisophthalic acid metal salt represented by the following formula (I'b) is preferred.

[0070]

[0071] In the above formula (Ib), R B and R in the above formula (I) B same.

[0072] In the above formula (I'b), R B , M and n are the same as R in the above formula (I') B , M and n are the same.

[0073] The position of the sulfo group in sulfoisophthalic acid or metal sulfoisophthalic acid salt may be 2-, 4-, 5- or 6-position, but preferably substituted at the 5-position as represented by the following formula (Ic) or (I′c).

[0074]

[0075] In the above formula (Ic), R B and R in the above formula (I) B same.

[0076] In the above formula (I'c), R B , M and n are the same as R in the above formula (I') B , M and n are the same.

[0077] In the polyester resin (X), examples of the sulfoisophthalic acid or sulfoisophthalic acid metal salt represented by the above-mentioned formula (Ic) or formula (I'c) include 5-sulfoisophthalic acid, sodium 5-sulfoisophthalate, lithium 5-sulfoisophthalate, potassium 5-sulfoisophthalate, calcium bis(5-sulfoisophthalate), dimethyl sodium 5-sulfoisophthalate, diethyl sodium 5-sulfoisophthalate, and the like.

[0078] When the polyester resin (X) contains a structural unit derived from at least one selected from the group consisting of sulfophthalic acid and a metal salt of sulfophthalic acid, it is preferred that the polyester resin (X) contains at least a structural unit derived from a metal salt of sulfophthalic acid. The content of the structural unit derived from sulfophthalic acid and the metal salt of sulfophthalic acid in the polyester resin is preferably 0.01 to 15 mol %, more preferably 0.03 to 10.0 mol %, further preferably 0.06 to 5.0 mol %, and further preferably 0.08 to 2.0 mol % based on the total amount of the structural unit derived from the dicarboxylic acid.

[0079] Examples of the alicyclic dicarboxylic acid include cyclohexanedicarboxylic acid, norbornenedicarboxylic acid, and tricyclodecanedicarboxylic acid.

[0080] Examples of the aliphatic dicarboxylic acid include malonic acid, succinic acid, adipic acid, azelaic acid, and sebacic acid.

[0081] Examples of the diol unit include a structural unit derived from an aliphatic diol, a structural unit derived from an alicyclic diol, and a structural unit derived from an aromatic diol. A structural unit derived from an aliphatic diol is preferred.

[0082] Examples of the aliphatic diol include ethylene glycol, 2-butene-1,4-diol, trimethylene glycol, 1-tetramethylene butanediol, hexamethylene glycol, neopentyl glycol, methylpentanediol, and diethylene glycol. Among them, ethylene glycol is preferred.

[0083] Examples of the alicyclic diol include cyclohexanedimethanol, isosorbide, spirodiol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, norbornene dimethanol, and tricyclodecanedimethanol.

[0084] Examples of the aromatic diol include bisphenol compounds and hydroquinone compounds.

[0085] The polyester resin (X) may have a structural unit derived from a hydroxycarboxylic acid.

[0086] Examples of the hydroxycarboxylic acid include aliphatic hydroxycarboxylic acids, alicyclic hydroxycarboxylic acids, and aromatic hydroxycarboxylic acids.

[0087] Examples of the aliphatic hydroxycarboxylic acid include 10-hydroxyoctadecanoic acid, lactic acid, hydroxyacrylic acid, 2-hydroxy-2-methylpropionic acid, and hydroxybutyric acid.

[0088] Examples of the alicyclic hydroxycarboxylic acid include hydroxymethylcyclohexanecarboxylic acid, hydroxymethylnorbornenecarboxylic acid, and hydroxymethyltricyclodecanecarboxylic acid.

[0089] Examples of the aromatic hydroxycarboxylic acid include hydroxybenzoic acid, hydroxymethylbenzoic acid, hydroxynaphthoic acid, 3-(hydroxyphenyl)propionic acid, hydroxyphenylacetic acid, and 3-hydroxy-3-phenylpropionic acid.

[0090] The polyester resin (X) may have a structural unit derived from a monofunctional compound and a structural unit derived from a polyfunctional compound.

[0091] Examples of the monofunctional compound include monocarboxylic acids and monoalcohols. Specifically, examples include aromatic monocarboxylic acids, aliphatic monocarboxylic acids, aromatic monoalcohols, aliphatic monoalcohols, and alicyclic monoalcohols.

[0092] Examples of the polyfunctional compound include aromatic polycarboxylic acids, alicyclic polycarboxylic acids, aliphatic polyols, alicyclic polyols, and esters thereof.

[0093] The polyester resin (X) preferably has a structural unit derived from a dicarboxylic acid, wherein the structural unit derived from the dicarboxylic acid contains a structural unit derived from terephthalic acid, and the structural unit derived from the diol contains a structural unit derived from ethylene glycol. It is more preferred that the polyester resin (X) has a structural unit derived from a dicarboxylic acid containing 80 mol% or more of a structural unit derived from terephthalic acid, and a structural unit derived from a diol containing 80 mol% or more of a structural unit derived from ethylene glycol. It is further preferred that the polyester resin (X) has a structural unit derived from a dicarboxylic acid containing 90 mol% or more of a structural unit derived from terephthalic acid, and a structural unit derived from a diol containing 90 mol% or more of a structural unit derived from ethylene glycol. It is further preferred that the polyester resin (X) has a structural unit derived from a dicarboxylic acid containing 98 mol% or more of a structural unit derived from terephthalic acid, and a structural unit derived from a diol containing substantially 100 mol% of a structural unit derived from ethylene glycol.

[0094] Specific examples of the polyester resin (X) include polyethylene terephthalate (PET).

[0095] Polyethylene terephthalate (PET) may contain structural units derived from aromatic dicarboxylic acids other than terephthalic acid. As aromatic dicarboxylic acids other than terephthalic acid, at least one selected from isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, and 4,4'-biphenyl dicarboxylic acid is preferred. These are low in cost, and copolyester resins containing these are easy to manufacture.

[0096] Among them, isophthalic acid and naphthalene dicarboxylic acid are preferred, and isophthalic acid is more preferred. Polyethylene terephthalate containing a structural unit derived from isophthalic acid is excellent in terms of excellent moldability and slow crystallization rate to prevent whitening of molded products. In addition, polyethylene terephthalate containing a structural unit derived from naphthalene dicarboxylic acid increases the glass transition point of the resin, improves heat resistance, and absorbs ultraviolet rays. Therefore, it is suitable for manufacturing multilayer containers that require resistance to ultraviolet rays. It should be noted that from the perspective of easy manufacturing and high economic efficiency, 2,6-naphthalene dicarboxylic acid components are preferred as naphthalene dicarboxylic acid.

[0097] When polyethylene terephthalate contains structural units derived from aromatic dicarboxylic acids other than terephthalic acid, the proportion of the structural units derived from aromatic dicarboxylic acids other than terephthalic acid is preferably 1 to 20 mol %, more preferably 1 to 10 mol %, and even more preferably 1 to 5 mol % of the dicarboxylic acid units.

[0098] Among them, when polyethylene terephthalate contains a structural unit derived from isophthalic acid, the ratio of the structure derived from isophthalic acid is preferably 1 to 20 mol %, more preferably 1 to 10 mol %, and even more preferably 1 to 5 mol % of the dicarboxylic acid unit.

[0099] In addition, the polyester resin (X) may be used alone or in combination of two or more kinds of resins.

[0100] The polyester resin (X) can be produced by a known method such as a direct esterification method or an ester exchange method.

[0101] The intrinsic viscosity of the polyester resin (X) is preferably 0.5 to 2.0 dL / g, more preferably 0.6 to 1.5 dL / g. When the intrinsic viscosity is at least 0.5 dL / g, the mechanical properties of the container will be excellent.

[0102] The intrinsic viscosity was measured by dissolving the polyester resin in a phenol / 1,1,2,2-tetrachloroethane (6 / 4 mass ratio) mixed solvent to prepare 0.2 g / dL, 0.4 g / dL, and 0.6 g / dL solutions, and measuring the solutions at 25° C. using an automatic viscosity meter (Viscotek, manufactured by Malvern).

[0103] (Other ingredients)

[0104] The polyester layer may contain other components, such as heat stabilizers, light stabilizers, moisture proof agents, water-proofing agents, lubricants, and spreading agents.

[0105] The polyester layer may contain resins other than the polyester resin (X) as a main component within a range not impairing the effects of the present invention. The content of the polyester resin (X) is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, relative to the total resin amount of the polyester layer.

[0106] <Polyamide layer>

[0107] The polyamide layer contains: a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B). In addition, the content of the polyamide resin (Y) contained in the polyamide layer is 0.05 to 7.0% by mass relative to the total amount of all polyamide layers and all polyester layers, and the yellowing inhibitor (A) is a dye, and the content of the yellowing inhibitor (A) is 1 to 30 ppm relative to the total amount of all polyamide layers and all polyester layers.

[0108] The polyamide layer provides a multilayer container with high oxygen barrier properties. In the present invention, the polyamide layer further contains an oxidation accelerator (B) and a yellowing inhibitor (A) as a dye, thereby achieving both extremely high oxygen barrier properties and yellowing inhibition of the recycled polyester produced from the multilayer container.

[0109] The reason why such an excellent effect is exerted is not limited, but is considered to be as follows.

[0110] In the present invention, the yellowing inhibitor (A) is included in the nitrogen-containing polyamide layer that is likely to cause yellowing of the recycled resin, thereby effectively inhibiting yellowing. However, if these yellowing inhibitors are allowed to coexist with an oxidizing accelerator, oxygen absorption by the oxidizing accelerator is inhibited. In the present invention, by using a specific amount of a dye that is not likely to inhibit oxidation reaction as a yellowing inhibitor and including it in the polyamide layer together with the oxidizing accelerator, it is believed that effective yellowing inhibition performance is exerted and oxygen absorption capacity can also be improved.

[0111] (Polyamide resin (Y))

[0112] Examples of the polyamide resin (Y) include xylylene-containing polyamide resins, nylon 6, nylon 66, nylon 666, nylon 610, nylon 11, nylon 12, and mixtures thereof. Among them, xylylene-containing polyamide resins are preferred from the viewpoints of improving gas barrier properties and being easily separated from the polyester layer during recycling. The xylylene-containing polyamide resin is preferably a polyamide resin containing a structural unit derived from xylylenediamine.

[0113] The xylylene-containing polyamide resin is obtained by polycondensing a diamine including xylylenediamine and a dicarboxylic acid, and has a structural unit derived from xylylenediamine and a structural unit derived from dicarboxylic acid. The xylylene-containing polyamide resin preferably contains 50 mol% or more of the structural unit derived from diamine (diamine unit), more preferably 70 mol% or more, further preferably 80 to 100 mol%, and further preferably 90 to 100 mol%.

[0114] The xylylenediamine is preferably m-xylylenediamine, p-xylylenediamine, or both thereof, and m-xylylenediamine is more preferred. Furthermore, the diamine unit constituting the xylylenediamine-containing polyamide resin preferably contains 50 mol% or more of a structural unit derived from m-xylylenediamine, more preferably 70 mol% or more, further preferably 80 to 100 mol%, and further preferably 90 to 100 mol%. By making the structural unit derived from m-xylylenediamine in the diamine unit within the above range, the gas barrier properties of the polyamide resin become better.

[0115] The diamine unit in the xylylenediamine-containing polyamide resin may be composed only of a structural unit derived from xylylenediamine, or may contain a structural unit derived from a diamine other than xylylenediamine. Here, examples of diamines other than xylylenediamine include linear or branched aliphatic diamines such as ethylenediamine, tetramethylenediamine, pentamethylenediamine, 2-methylpentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethyl-hexamethylenediamine, and 2,4,4-trimethyl-hexamethylenediamine; alicyclic diamines such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decahydronaphthalene, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, p-phenylenediamine, and bis(aminomethyl)naphthalene.

[0116] In the xylylene-containing polyamide resin, examples of compounds that can constitute the dicarboxylic acid unit include α,ω-straight-chain aliphatic dicarboxylic acids having 4 to 20 carbon atoms, such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; other aliphatic dicarboxylic acids such as dimer acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, xylene dicarboxylic acid, and naphthalene dicarboxylic acid. Preferred are α,ω-straight-chain aliphatic dicarboxylic acids having 4 to 20 carbon atoms, more preferred are adipic acid and sebacic acid, and from the viewpoint of achieving good barrier properties, adipic acid is further preferred.

[0117] The xylylene group-containing polyamide resin preferably contains 50 mol% or more, more preferably 70 mol% or more, further preferably 80 to 100 mol%, and further preferably 90 to 100 mol% of adipic acid-derived structural units among structural units derived from dicarboxylic acid (dicarboxylic acid units).

[0118] That is, the polyamide resin (Y) preferably comprises a structural unit derived from a diamine containing 50 mol % or more of a structural unit derived from xylylenediamine and a structural unit derived from a dicarboxylic acid containing 50 mol % or more of a structural unit derived from adipic acid, and more preferably comprises a structural unit derived from a diamine containing 80 mol % or more of a structural unit derived from xylylenediamine and a structural unit derived from a dicarboxylic acid containing 80 mol % or more of a structural unit derived from adipic acid.

[0119] As the xylylenediamine, meta-xylylenediamine is preferred.

[0120] In addition, as the remaining dicarboxylic acid unit excluding adipic acid, a structural unit derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms is preferred.

[0121] In addition, as a preferred xylylene-containing polyamide resin, there can be exemplified a polyamide resin in which 70 mol% or more of the diamine units are structural units derived from xylylenediamine (preferably m-xylylenediamine), 70 to 99 mol% of the dicarboxylic acid units are structural units derived from adipic acid, and 1 to 30 mol% are structural units derived from isophthalic acid. The polyamide resin is preferably a polyamide resin in which 80 mol% or more of the diamine units are structural units derived from m-xylylenediamine (preferably m-xylylenediamine), 80 to 99 mol% of the dicarboxylic acid units are structural units derived from adipic acid, and 1 to 20 mol% are structural units derived from isophthalic acid.

[0122] By adding an isophthalic acid unit as a dicarboxylic acid unit, the melting point is lowered and the molding temperature can be lowered, so that thermal degradation during molding can be suppressed. In addition, the stretching moldability is improved by delaying the crystallization time.

[0123] In addition to the aforementioned diamines and dicarboxylic acids, as components constituting the xylylene-containing polyamide resin, lactams such as ε-caprolactam and laurolactam, aliphatic aminocarboxylic acids such as aminocaproic acid and aminoundecanoic acid; and aromatic aminocarboxylic acids such as p-aminomethylbenzoic acid may be used as copolymer components within the range not impairing the effects of the present invention.

[0124] The xylylene-containing polyamide resin is preferably produced by a polycondensation reaction in a molten state (hereinafter, sometimes referred to as "melt polycondensation"). For example, it is preferably produced by the following method: a nylon salt composed of a diamine and a dicarboxylic acid is heated by a pressure method in the presence of water, and polymerized in a molten state while removing the water. In addition, it can also be produced by directly adding a diamine to a dicarboxylic acid in a molten state and performing polycondensation under normal pressure. In this case, in order to keep the reaction system in a uniform liquid state, it is preferred to continuously add a diamine to the dicarboxylic acid, during which the reaction system is heated in a manner that the reaction temperature is not lower than the melting point of the generated oligoamide and polyamide, and the polycondensation is carried out. In addition, the xylylene-containing polyamide can be further solid-phase polymerized as needed to increase the molecular weight.

[0125] The xylylene group-containing polyamide resin is preferably polycondensed in the presence of a phosphorus atom-containing compound. When the xylylene group-containing polyamide resin is polycondensed in the presence of a phosphorus atom-containing compound, processing stability during melt molding can be improved, and coloration can be easily suppressed.

[0126] As the phosphorus atom-containing compound, a hypophosphorous acid compound and a phosphorous acid compound are preferred, and a hypophosphorous acid compound is more preferred.

[0127] The phosphorus atom-containing compound is preferably an organic metal salt, and among them, an alkali metal salt is more preferred.

[0128] From the viewpoint of promoting the polymerization reaction and preventing coloration, examples of the hypophosphorous acid compound include hypophosphorous acid, metal hypophosphorous acid salts, metal phenylphosphite salts, ethyl hypophosphite, dimethylphosphinic acid, phenylmethylphosphinic acid, phenylphosphite, and ethyl phenylphosphite, and metal hypophosphite is preferred.

[0129] Examples of the metal hypophosphite salt include sodium hypophosphite, potassium hypophosphite, lithium hypophosphite and calcium hypophosphite, and sodium hypophosphite is more preferred.

[0130] Examples of the phenylphosphite metal salt include sodium phenylphosphite, potassium phenylphosphite and lithium phenylphosphite.

[0131] Examples of the phosphorous acid compound include phosphorous acid, pyrophosphorous acid, phosphorous acid metal salts, phenylphosphonic acid metal salts, triethyl phosphite, triphenyl phosphite, ethylphosphonic acid, phenylphosphonic acid, and diethyl phenylphosphonate.

[0132] Examples of the phosphorous acid metal salt include sodium hydrogen phosphite, sodium phosphite, potassium phosphite, and calcium phosphite.

[0133] Examples of the phenylphosphonic acid metal salt include sodium ethylphosphonate, potassium ethylphosphonate, sodium phenylphosphonate, potassium phenylphosphonate, lithium phenylphosphonate and the like.

[0134] The phosphorus atom-containing compound may be used alone or in combination of two or more.

[0135] In addition, the polycondensation of the xylylene-containing polyamide resin is preferably carried out in the presence of a phosphorus atom-containing compound and an alkali metal compound. If the amount of the phosphorus atom-containing compound is too large, there is a concern that the polyamide resin may gel. Therefore, from the viewpoint of adjusting the amidation reaction rate, it is preferred to allow the alkali metal compound to coexist.

[0136] Examples of the alkali metal compound include alkali metal hydroxides and alkali metal acetates. Examples of the alkali metal hydroxides include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide. Examples of the alkali metal acetates include lithium acetate, sodium acetate, potassium acetate, rubidium acetate, and cesium acetate.

[0137] When an alkali metal compound is used for polycondensation of a polyamide resin, the amount of the alkali metal compound used is preferably 0.5 to 1, more preferably 0.55 to 0.95, and even more preferably 0.6 to 0.9, from the viewpoint of suppressing the formation of gel, in which the value obtained by dividing the number of moles of the alkali metal compound by the number of moles of the phosphorus atom-containing compound is.

[0138] The number average molecular weight of the polyamide resin can be appropriately selected depending on the application and molding method of the multilayer container, and is preferably 10,000 to 60,000, more preferably 11,000 to 50,000, from the viewpoint of moldability and strength of the multilayer container.

[0139] In addition, the number average molecular weight of the polyamide resin is calculated by the following formula (X).

[0140] Number average molecular weight = 2 × 1,000,000 / ([COOH] + [NH2])… (X)

[0141] (Wherein, [COOH] represents the terminal carboxyl concentration in the polyamide resin (μmol / g), and [NH2] represents the terminal amino concentration in the polyamide resin (μmol / g).)

[0142] Here, the terminal amino group concentration used is a value obtained by dissolving a polyamide resin in a phenol / ethanol mixed solution and then performing neutralization titration on the obtained solution using a dilute hydrochloric acid aqueous solution, and the terminal carboxyl group concentration used is a value obtained by dissolving a polyamide in benzyl alcohol and then performing neutralization titration on the obtained solution using a sodium hydroxide aqueous solution.

[0143] The content of the polyamide resin (Y) contained in the polyamide layer is 0.05 to 7.0% by mass relative to the total amount of all polyamide layers and all polyester layers, and is preferably 0.5 to 6.0% by mass, more preferably 1.0 to 5.0% by mass, and further preferably 1.5 to 4.5% by mass from the viewpoint of gas barrier properties and suppression of yellowing of the recycled polyester.

[0144] (Yellowing Inhibitor (A))

[0145] The polyamide layer of the multi-layer container contains a yellowing inhibitor (A) which is a dye and has a content of 1 to 30 ppm based on the total amount of all polyamide layers and all polyester layers.

[0146] The content of the yellowing inhibitor (A) is 1 to 30 ppm relative to the total amount of all polyamide layers and all polyester layers, preferably 1.5 to 25 ppm from the viewpoint of effectively suppressing yellowing of the regenerated polyester, more preferably 2 to 22 ppm, further preferably 3 to 20 ppm, and further preferably 8 to 20 ppm from the viewpoint of mixing and molding properties during production.

[0147] It should be noted that "ppm" in the present invention means parts per million by mass.

[0148] From the viewpoint of effectively suppressing yellowing of the regenerated polyester, the content of the yellowing inhibitor (A) in the polyamide layer is preferably 0.001 to 1.0 mass %, more preferably 0.005 to 0.5 mass %, further preferably 0.008 to 0.1 mass %, and further preferably 0.03 to 0.08 mass %.

[0149] From the viewpoint of transparency, the yellowing inhibitor (A) is a dye, and among them, a blue dye is preferred.

[0150] By using a dye, yellowing of the regenerated polyester obtained from the multi-layer container of the present invention can be suppressed in an extremely small amount, and a regenerated polyester having excellent transparency can be obtained.

[0151] Here, "dye" refers to a colorant that is soluble in a solvent.

[0152] Examples of the dye include anthraquinone dyes, pyrazolone dyes, coumarin dyes, perinone dyes, methine dyes, and quinophthalone dyes, and anthraquinone dyes are preferred.

[0153] As anthraquinone dyes, anthraquinone dyes in which the hydrogen atoms of the aromatic ring are replaced by aromatic amines, aliphatic amines, and halogens can be cited, and anthraquinone dyes in which the hydrogen atoms of the aromatic ring are replaced by aromatic amines are preferred. By using such anthraquinone dyes, yellowing of the regenerated polyester can be suppressed. As anthraquinone dyes, anthraquinone dyes in which the hydrogen atoms of the aromatic ring are not replaced by hydroxyl groups are preferred. By using such anthraquinone dyes, high oxygen barrier properties can be obtained using the multilayer container of the present invention.

[0154] By using an anthraquinone-based dye, yellowing of the regenerated polyester obtained from the multi-layer container of the present invention can be suppressed in an extremely small amount.

[0155] As the anthraquinone-based dye, anthraquinone-based blue dye is more preferred.

[0156] As the anthraquinone dye, a compound represented by the following formula (1) is preferred.

[0157]

[0158] (In formula (1), n ​​represents the number of R, and each of the two n is independently 1 to 5. Each of the 2n Rs is independently an alkyl group having 1 to 4 carbon atoms.)

[0159] In formula (1), n ​​is 1 to 5, preferably 2 to 5, and more preferably 2 to 3. By setting n to the above range, yellowing (Δb * R each independently represents an alkyl group having 1 to 4 carbon atoms, preferably at least one selected from the group consisting of a methyl group and an ethyl group. R preferably substitutes at least the ortho or para position relative to the amino group, preferably substitutes at least the para position, more preferably substitutes at least the ortho position, and further preferably substitutes at the ortho and para positions.

[0160] Specific examples of the compound represented by formula (1) include 1,4-bis[(2-ethyl-6-methylphenyl)amino]anthraquinone, Solvent Blue 97, Solvent Blue 104, and Solvent Green 3, with 1,4-bis[(2-ethyl-6-methylphenyl)amino]anthraquinone, Solvent Blue 97, and Solvent Blue 104 being preferred.

[0161] Commercially available products of the yellowing inhibitor (A) include Macrolex Blue 3R (1,4-bis[(2-ethyl-6-methylphenyl)amino]anthraquinone, anthraquinone dye, manufactured by LANXESS), Macrolex Blue RR Gran (anthraquinone dye, manufactured by LANXESS), Oracet Blue 690 (anthraquinone dye, manufactured by BASF), and Quinizarin Green SS (anthraquinone dye, manufactured by Tokyo Chemical Industry Co., Ltd.).

[0162] (Oxidation accelerator (B))

[0163] In the multi-layer container of the present invention, the polyamide layer contains an oxidation accelerator (B) for the purpose of inducing an oxidation reaction of the polyamide resin (Y) to enhance the oxygen absorption function and further enhance the gas barrier properties.

[0164] The oxidation accelerator (B) is preferably a compound containing a transition metal, and more preferably at least one selected from the group consisting of a transition metal single substance, an oxide, an inorganic acid salt, an organic acid salt, and a complex.

[0165] Examples of the inorganic acid salt include halides such as chlorides and bromides, carbonates, sulfates, nitrates, phosphates, and silicates.

[0166] Examples of the organic acid salt include carboxylates, sulfonates, and phosphonates.

[0167] Examples of the complex include complexes with β-diketone, β-ketoester, and the like.

[0168] The transition metal is preferably a transition metal of Group VIII of the periodic table, and from the viewpoint of exhibiting oxygen absorbing ability, at least one selected from the group consisting of cobalt, iron, manganese, and nickel is more preferred, and cobalt is further preferred.

[0169] From the viewpoint of exhibiting good oxygen absorption ability, among the compounds containing transition metals, specifically, at least one selected from the group consisting of carboxylates, carbonates, acetylacetonate complexes, oxides and halides containing transition metals is preferred, and at least one selected from the group consisting of octanoates, neodecanoates, naphthenates, stearates, acetates, carbonates and acetylacetonate complexes is preferred, and cobalt formate such as cobalt octanoate, cobalt naphthenate, cobalt acetate, cobalt neodecanoate and cobalt stearate is further preferred.

[0170] The oxidation accelerator (B) may be used alone or in combination of two or more.

[0171] From the viewpoint of improving the gas barrier properties and suppressing yellowing of the recycled polyester resin, the content of the oxidation accelerator (B) is preferably 0.0001 to 1.0 mass %, more preferably 0.01 to 0.8 mass %, and even more preferably 0.05 to 0.6 mass % based on the polyamide layer.

[0172] From the viewpoint of improving gas barrier properties and suppressing yellowing of the recycled polyester resin, the content of the oxidation accelerator (B) is preferably 0.0001 to 1.0 part by mass, more preferably 0.01 to 0.8 part by mass, and even more preferably 0.05 to 0.6 part by mass based on 100 parts by mass of the polyamide resin (Y).

[0173] Furthermore, from the viewpoint of improving gas barrier properties and suppressing yellowing of the recycled polyester resin, the content of the transition metal in the oxidation accelerator (B) is preferably 0.00001 to 0.1 mass %, more preferably 0.0001 to 0.08 mass %, and even more preferably 0.0003 to 0.06 mass % relative to the polyamide layer.

[0174] In addition, from the viewpoint of improving the gas barrier properties and suppressing the yellowing of the recycled polyester resin, the content of the transition metal in the oxidation accelerator (B) is preferably 0.00001 to 0.1 parts by mass, more preferably 0.0001 to 0.08 parts by mass, and still more preferably 0.0003 to 0.06 parts by mass relative to 100 parts by mass of the polyamide resin (Y). It should be noted that when a carboxylate containing a transition metal is used as the oxidation accelerator (B), the content of the transition metal refers to the content of the transition metal itself in the compound containing the transition metal.

[0175] (Greening Inhibitor (C))

[0176] The polyamide layer of the multilayer container preferably comprises a greening inhibitor (C).

[0177] The greening inhibitor (C) is used to inhibit the greening of the recycled polyester formed by recycling the multilayer container of the present invention. * Direction green.

[0178] The content of the greening inhibitor (C) is 1 to 30 ppm relative to the total amount of all polyamide layers and all polyester layers, preferably 1.5 to 25 ppm from the viewpoint of effectively inhibiting the greening of the recycled polyester, more preferably 2 to 22 ppm, and further preferably 3 to 20 ppm from the viewpoint of mixing and molding properties during production.

[0179] It should be noted that "ppm" in the present invention means parts per million by mass.

[0180] From the viewpoint of effectively suppressing greening of the regenerated polyester, the content of the greening inhibitor (C) in the polyamide layer is preferably 0.001 to 1.0 mass %, more preferably 0.005 to 0.5 mass %, further preferably 0.008 to 0.1 mass %, and further preferably 0.01 to 0.08 mass %.

[0181] The mass ratio [(A) / (C)] of the yellowing inhibitor (A) to the greening inhibitor (C) in the polyamide layer of the multi-layer container of the present invention is preferably 20 / 80 to 80 / 20, more preferably 30 / 70 to 70 / 30, and even more preferably 40 / 60 to 60 / 40.

[0182] When the mass ratio is within this range, the color change of the recycled polyester obtained after recycling is small, and in particular, a polyester excellent in colorlessness can be obtained.

[0183] From the viewpoint of transparency, the greening inhibitor (C) is preferably a dye.

[0184] Among dyes, at least one selected from the group consisting of anthraquinone dyes and azo dyes is also preferred, and anthraquinone dyes are more preferred from the viewpoint of heat resistance.

[0185] Here, "dye" refers to a colorant that is soluble in a solvent.

[0186] The anthraquinone dye is preferably one in which the hydrogen atoms of the aromatic ring are not substituted with hydroxyl groups. By using such anthraquinone dye, the multi-layer container of the present invention can obtain high oxygen barrier properties.

[0187] The greening inhibitor (C) is preferably a red dye, more preferably at least one selected from the group consisting of anthraquinone red dyes and azo red dyes, and further preferably anthraquinone red dyes from the viewpoint of heat resistance.

[0188] By using an anthraquinone-based red dye and an azo-based red dye, greening of the regenerated polyester obtained from the multi-layer container of the present invention can be suppressed in an extremely small amount.

[0189] As the anthraquinone dye, a compound represented by the following formula (2) is preferred.

[0190]

[0191] (In formula (2), two Ys each independently represent a hydrogen atom or a group represented by formula (2a). Among them, at least one Y is a group represented by formula (2a).

[0192] In formula (2a), R represents an alkyl group having 1 to 4 carbon atoms.

[0193] In formula (2), two Ys each independently represent a hydrogen atom or a group represented by formula (2a), but at least one Y is a group represented by formula (2a), and preferably one Y is a group represented by formula (2a) and the remaining Ys are hydrogen atoms.

[0194] In formula (2a), R represents an alkyl group having 1 to 4 carbon atoms, preferably at least one selected from the group consisting of a methyl group and an ethyl group. It should be noted that when two Ys are groups represented by formula (2a), the Rs in the two groups represented by formula (2a) may be the same or different. Preferably, R is substituted in the para position relative to the amino group.

[0195] As a specific compound represented by formula (2), Solvent Violet 36 can be mentioned.

[0196] The greening inhibitor (B) may be used alone or in combination of two or more.

[0197] Examples of commercially available products of the greening inhibitor (B) include MACROLEX Violet 3R Gran (anthraquinone dye, manufactured by LANXESS), MACROLEX Red Violet R Gran (Disperse Violet 31, Disperse Violet 26, Solvent Violet 59, anthraquinone dye, manufactured by LANXESS), MACROLEX Red 5B Gran (Disperse Violet 31, Disperse Violet 26, Solvent Violet 59, anthraquinone dye, manufactured by LANXESS), and MACROLEX Red B (Solvent Red 195, azo dye, manufactured by LANXESS).

[0198] (Polyester resin (Z))

[0199] From the viewpoint of suppressing yellowing of the recycled polyester and improving impact resistance, the polyamide layer of the multi-layer container preferably contains a polyester resin (Z).

[0200] The polyester resin (Z) used in the polyamide layer is preferably the polyester resin described in the item (polyester resin (X)) contained in the above polyester layer, and the same applies to suitable polyester resins.

[0201] Specifically, the polyester resin (Z) is preferably polyethylene terephthalate (PET). The polyethylene terephthalate may contain a structural unit derived from an aromatic dicarboxylic acid other than terephthalic acid, and the structural unit derived from an aromatic dicarboxylic acid other than terephthalic acid is preferably a structural unit derived from sulfophthalic acid or a sulfophthalic acid metal salt. The sulfophthalic acid metal salt is a metal salt of sulfophthalic acid, and examples of the metal atom include alkali metals and alkaline earth metals.

[0202] By including the polyester resin (Z) in the polyamide layer, yellowing of the recycled polyester obtained by recycling is suppressed and the adhesion between the polyamide layer and the polyester layer is improved, thereby improving the impact resistance of the multi-layer container.

[0203] (Other ingredients)

[0204] The polyamide layer may contain other components, such as heat stabilizers, light stabilizers, moisture proof agents, water repellents, lubricants, and spreaders.

[0205] The polyamide layer may contain a resin other than the polyamide resin (Y) as a main component within a range not impairing the effects of the present invention.

[0206] When the yellowing inhibitor (A) is mixed by the masterbatch method described below, it is particularly preferred to contain a polyamide resin or polyester resin used in the masterbatch. In this case, the amount of the polyamide resin or polyester resin used in the masterbatch relative to the total amount of the polyamide layer is preferably 1 to 20% by mass, more preferably 3 to 15% by mass.

[0207] (Resin composition in polyamide layer)

[0208] From the viewpoint of gas barrier properties, the content of the polyamide resin (Y) in the polyamide layer is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, based on the total resin amount of the polyamide layer.

[0209] In addition, when the polyamide layer contains a polyester resin (Z), from the viewpoint of impact resistance and gas barrier properties, the content of the polyester resin (Z) in the polyamide layer is preferably 5 to 70% by mass, more preferably 10 to 65% by mass, further preferably 20 to 65% by mass, and further preferably 40 to 65% by mass. When the content of the polyester resin (Z) is within the above range, the multilayer container of the present invention suppresses yellowing of the recycled polyester obtained by recycling, and the adhesion between the polyamide layer and the polyester layer is improved, thereby improving the impact resistance.

[0210] <Structure / Characteristics of Multilayer Container>

[0211] The multi-layer container of the present invention has a multi-layer structure having: a polyester layer comprising a polyester resin (X); and a polyamide layer comprising a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B).

[0212] The multilayer container of the present invention may include the polyester layer and a resin layer other than the polyamide layer. However, from the viewpoint of facilitating classification during recycling and improving the yellowing suppression effect, the content of the polyester layer and the resin layer other than the polyamide layer is preferably small, and the polyester layer and the resin layer other than the polyamide layer are preferably substantially free. In addition, an adhesive layer formed of an adhesive and an inorganic layer formed of an inorganic substance may be provided. However, from the viewpoint of facilitating classification during recycling and improving the yellowing suppression effect, the content of the adhesive layer and the inorganic layer is preferably small, and the adhesive layer and the inorganic layer are preferably substantially free.

[0213] The multilayer container of the present invention has a multilayer structure of two or more layers, preferably a 2-5 layer structure, more preferably a 3-5 layer structure, further preferably a 3-layer structure or a 5-layer structure, and further preferably a 3-layer structure.

[0214] The outermost layer of the multilayer container of the present invention is preferably a polyester layer. In addition, the innermost layer is preferably also a polyester layer, and more preferably both the outermost layer and the innermost layer are polyester layers.

[0215] When the outermost layer is a polyester layer, the multi-layer container will be excellent in impact resistance, appearance, and design.

[0216] Here, the "outermost layer" refers to a layer on the surface of the outer side of the multilayer container, which is in contact with packaging materials, fasteners, etc. during transportation and is related to the appearance of the container. In addition, the "innermost layer" refers to a layer on the surface of the inner side of the multilayer container, which is in contact with the contents, preferably the liquid.

[0217] Therefore, as for the structure of the multilayer container, it is preferred that the multilayer container has a 2-5 layer structure in which the outermost layer is a polyester layer, and it is more preferred that the multilayer container has a 3-5 layer structure in which the outermost layer and the innermost layer are polyester layers.

[0218] In the case of a two-layer structure, it is preferably polyamide layer / polyester layer from the innermost layer, in the case of a three-layer structure, it is preferably polyester layer / polyamide layer / polyester layer from the innermost layer, and in the case of a five-layer structure, it is preferably polyester layer / polyamide layer / polyester layer / polyamide layer / polyester layer from the innermost layer.

[0219] The multilayer container of the present invention is preferably a hollow container. When the multilayer container is a hollow container, the main body has at least a multilayer structure. In addition, the ratio of the thickness (W) of the polyester layer in the main body to the thickness (S) of the polyamide layer (thickness ratio W / S) is preferably 2.5 or more and 200 or less. It should be noted that the thickness of the polyester layer refers to the average thickness. When there are multiple layers of the polyester layer in the main body, the thickness of the multiple layers is averaged to find the average thickness of each layer. The thickness of the polyamide layer is also the same.

[0220] If the thickness ratio W / S is 2.5 or more, it is preferred that the polyamide resin can be easily classified from the polyester resin in the classification process, especially in the air separation and specific gravity separation in the production method of the recycled polyester. In addition, if the thickness ratio W / S is 200 or less, the gas barrier property of the hollow container is excellent, and the content can be stored for a long time.

[0221] The thickness ratio (W / S) is more preferably 3 to 50, and even more preferably 4 to 15, from the viewpoint of improving the classifying property in the classifying step and improving the gas barrier property of the hollow container.

[0222] In addition, when the multilayer container is a hollow container, the total thickness of the main body of the hollow container (i.e., the total thickness of all layers of the main body) is preferably 100 μm to 5 mm, more preferably 150 μm to 3 mm, and further preferably 200 μm to 2 mm. In addition, the thickness (W) of each polyester layer is preferably 30 μm to 2 mm, more preferably 40 μm to 1 mm, and further preferably 50 μm to 500 μm. The thickness (S) of each polyamide layer is preferably 1 to 200 μm, more preferably 3 to 100 μm, and further preferably 8 to 50 μm. In the present invention, by making the thickness of the polyamide layer within this range, gas barrier properties are ensured, and in the classification process, the polyamide layer becomes easy to be classified from the polyester.

[0223] When the multi-layer container is a hollow container, the polyamide layer is preferably present on more than 50% of the surface area of ​​the outer surface of the container, more preferably on more than 70% of the surface area of ​​the outer surface of the container, further preferably on more than 90% of the surface area of ​​the outer surface of the container, further preferably on more than 99% of the surface area of ​​the outer surface of the container, further preferably substantially on 100% of the surface area of ​​the outer surface of the container, and further preferably on 100% of the surface area of ​​the outer surface of the container, from the viewpoint of achieving good gas barrier properties.

[0224] When the multilayer container of the present invention is a hollow container, it is more preferably a liquid packaging container filled with liquid inside the hollow container, and is further preferably a beverage packaging container. Examples of the liquid filled inside include beverages, liquid flavoring agents, chemicals, medicines, detergents, etc., and beverages that can be effectively prevented from deteriorating due to oxygen by using the multilayer container of the present invention are preferred.

[0225] Examples of beverages include water, carbonated water, oxygenated water, hydrogenated water, milk, dairy products, fruit juices, coffee, coffee drinks, carbonated soft drinks, teas, and alcoholic beverages.

[0226] Examples of liquid seasonings include sauces, soy sauces, syrups, mirin, and seasonings.

[0227] Examples of the chemical products include agricultural chemicals and insecticides.

[0228] The oxygen barrier property of the multilayer container of the present invention can be evaluated according to the oxygen permeability test based on the MOCON method in accordance with ASTM D3985. When a total amount of 25 g of a resin having a mass ratio of a polyester layer to a polyamide layer of 97:3 is made into a three-layer hollow container with an internal volume of 500 mL, the oxygen permeability (cc / (bottle·0.21atm·day)) of the multilayer container of the present invention is preferably 0.020 or less, more preferably 0.010 or less, and further preferably 0.005 or less. It should be noted that the manufacture of the three-layer hollow container can be based on the method of the embodiment.

[0229] The measurement was performed using OX-TRAN2 / 61 manufactured by MOCON. The aforementioned 500 mL container was filled with 100 mL of water. Under conditions of an oxygen partial pressure of 0.21 atm, a temperature of 23°C, a humidity of 100% RH inside the container, and an external humidity of 50% RH, 1 atm of nitrogen was circulated inside the container at a rate of 20 mL / min. The oxygen contained in the nitrogen after circulation inside the container was detected by a coulometric sensor for measurement.

[0230] [Method for manufacturing multi-layer container]

[0231] The method for producing the multi-layered container of the present invention is not limited, but it is preferably produced by the following method.

[0232] The method for producing a multi-layer container of the present invention preferably comprises the following steps: step 1, mixing a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B) to prepare a polyamide resin mixture; step 2, co-injection molding the polyamide resin mixture and a polyester resin composition containing a polyester resin (X) to obtain a multi-layer preform; and step 3, blow molding the multi-layer preform, wherein the multi-layer container comprises: a polyester layer containing a polyester resin (X); and a polyamide layer containing a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B), wherein the content of the polyamide resin (Y) is 0.05 to 7.0% by mass relative to the total amount of all polyamide layers and all polyester layers, and the yellowing inhibitor (A) is a dye, and the content of the yellowing inhibitor (A) is 1 to 30 ppm relative to the total amount of all polyamide layers and all polyester layers.

[0233] <Step 1 (Step of Preparing a Polyamide Resin Mixture)>

[0234] In step 1, a polyamide resin (Y), a yellowing inhibitor (A), and an oxidation accelerator (B) are mixed to prepare a polyamide resin mixture.

[0235] In general, in order to spread the yellowing inhibitor throughout the entire container, a device for stirring and mixing or kneading the yellowing inhibitor with all the resins is required. However, in the method for producing a multi-layer container of the present invention, by mixing the yellowing inhibitor (A) and the oxidation accelerator (B) with a small amount of the polyamide resin (Y), the yellowing inhibitor can be effectively spread throughout the entire container in a small-scale and short-time mixing, thereby achieving excellent productivity.

[0236] The mixing method may be dry blending or melt blending (melt kneading). From the viewpoint of reducing the thermal history and preventing the degradation of the resin and the yellowing inhibitor, dry blending and melt blending by the masterbatch method are preferred. In addition, from the viewpoint of preventing the yellowing inhibitor from adhering to the molding machine and the periphery of the molding machine and remaining in step 2, melt blending is preferred. Among them, from the viewpoint of reducing the thermal history and preventing the degradation of the resin and the yellowing inhibitor, the masterbatch method is preferred.

[0237] In step 1, the pelletized polyamide resin (Y) is preferably mixed with the yellowing inhibitor (A) and the oxidation accelerator (B) at 230°C or less, more preferably at 150°C or less, and further preferably at 100°C or less. By mixing at 230°C or less, the thermal history can be reduced, and the degradation of the resin and the yellowing inhibitor can be prevented. This is considered to be because the polyamide resin can maintain the pelletized form, so the thermal degradation is small. When mixing at 230°C or less, dry mixing is preferably performed.

[0238] The yellowing inhibitor (A) preferably used in the step 1 is the same as described in the above item (yellowing inhibitor (A)), and is a dye, and an anthraquinone-based dye is more preferable.

[0239] The yellowing inhibitor (A) is preferably in a powder form, a dispersion or a solution, and more preferably in a powder form. When the yellowing inhibitor (A) is in these forms, it can be mixed more easily and uniformly with the polyamide resin (Y).

[0240] The oxidation accelerator (B) preferably used in step 1 is the same as that described in the above item (Oxidation accelerator (B)). Specifically, it is preferably a compound containing a transition metal, preferably at least one selected from the group consisting of carboxylates, carbonates, acetylacetonate complexes, oxides and halides containing transition metals, more preferably at least one selected from octanoates, neodecanoates, naphthenates, stearates, acetates, carbonates and acetylacetonate complexes, and further preferably cobalt formate such as cobalt octanoate, cobalt naphthenate, cobalt acetate, cobalt neodecanoate and cobalt stearate.

[0241] In the step 1, it is preferred that a greening inhibitor (C) is further mixed.

[0242] The greening inhibitor (C) suitably used in step 1 is the same as those described in the item (Greening inhibitor (C)) above, and is preferably at least one selected from the group consisting of dyes and pigments, more preferably at least one selected from the group consisting of anthraquinone dyes and azo dyes, further preferably at least one selected from the group consisting of anthraquinone red dyes and azo red dyes, and from the viewpoint of heat resistance, anthraquinone red dyes are further preferred.

[0243] The greening inhibitor (C) is preferably in a powder form, a dispersion or a solution, and more preferably in a powder form. The greening inhibitor (C) in these forms can be mixed more easily and uniformly with the polyamide resin (Y).

[0244] Furthermore, in step 1, it is preferred to mix a polyester resin (Z).

[0245] The polyester resin (Z) preferably used in step 1 is the same as that described in the above item (Polyester resin (Z)). When mixing by dry blending, the polyester resin (Z) is preferably mixed in the form of pellets.

[0246] Examples of a mixing apparatus used for dry blending include a tumble mixer, a ribbon mixer, a Henschel mixer, and a Banbury mixer.

[0247] In step 1, examples of a method for mixing the polyamide resin (Y), the yellowing inhibitor (A) and the oxidation accelerator (B) by melt blending include a masterbatch method and a full mixing method, and a masterbatch method is preferred.

[0248] The masterbatch method is a method in which, in step 1, a polyamide resin or a polyester resin is kneaded with a yellowing inhibitor (A) and an oxidation accelerator (B), and then mixed with a polyamide resin (Y).

[0249] The masterbatch method is a method in which a small amount of polyamide resin or polyester resin is kneaded with a yellowing inhibitor (A) and an oxidation accelerator (B) to form a masterbatch, and then mixed with the remaining amount of polyamide resin (Y). In addition, when obtaining the masterbatch, a greening inhibitor (C) may also be kneaded at the same time. That is, in step 1, it is preferred that the polyamide resin or polyester resin is kneaded with the yellowing inhibitor (A) and the oxidation accelerator (B), and then mixed with the polyamide resin (Y). In step 1, it is more preferred that the polyamide resin or polyester resin, the yellowing inhibitor (A), the oxidation accelerator (B) and the greening inhibitor (C) are kneaded, and then mixed with the polyamide resin (Y).

[0250] In the masterbatch, polyamide resin or polyester resin is preferably used. From the perspective of compatibility with the polyamide resin (Y), polyamide resin is preferably used, and from the perspective of suppressing yellowing due to thermal history, polyester resin is preferably used. It should be noted that these may be used in mixture.

[0251] In particular, the yellowing inhibitor (A) is preferably prepared as a masterbatch kneaded with a polyamide resin (a masterbatch containing a polyamide resin and the yellowing inhibitor (A), or a polyamide resin composition), and the oxidation accelerator (B) is preferably prepared as a masterbatch kneaded with a polyester resin (a masterbatch containing a polyester resin and the oxidation accelerator (B), or a polyester resin composition). In addition, the greening inhibitor (C) is preferably prepared as a masterbatch kneaded with a polyamide resin (a masterbatch containing a polyamide resin, the yellowing inhibitor (A) and the greening inhibitor (C), or a polyamide resin composition).

[0252] The polyamide resin used in the masterbatch is preferably the polyamide resin (Y), and more preferably the same as the remaining polyamide resin (Y).

[0253] The polyester resin used in the masterbatch is preferably a polyester resin (Z). Alternatively, the same polyester resin as the polyester resin (X) may be used, or the same polyester resin as the polyester resin (X) of the polyester layer may be used.

[0254] The amount of the polyamide resin or polyester resin used in the masterbatch is preferably 1 to 20% by mass, more preferably 3 to 15% by mass, based on the total amount of the polyamide layer.

[0255] As a method for obtaining a masterbatch, when a polyamide resin or a polyester resin is kneaded with a yellowing inhibitor (A) and an oxidation accelerator (B), when the melting point of the resin used for the masterbatch is Tm, from the viewpoint of sufficient mixing, the kneading temperature (°C) is preferably Tm+5 to Tm+60, more preferably Tm+10 to Tm+50, and further preferably Tm+15 to Tm+40. Specifically, it is further preferably 245 to 300°C, further preferably 250 to 290°C, and further preferably 255 to 280°C. In addition, from the viewpoint of sufficient mixing, the kneading time is preferably 10 to 600 seconds, more preferably 20 to 400 seconds, and further preferably 30 to 300 seconds. As the apparatus used for kneading, an open type stirring roll, a non-open type Banbury mixer, a kneader, a continuous kneading machine (single screw kneading machine, twin screw kneading machine, multi-screw kneading machine, etc.) and the like can be cited.

[0256] In addition, as a method for mixing the masterbatch with the remaining polyamide resin (Y), dry blending and further kneading can be mentioned. From the viewpoint of reducing the thermal history, dry blending is preferred. In dry blending, it is preferred that pellets of the masterbatch and pellets of the remaining polyamide resin (Y) are mixed with a mixing device such as a tumble mixer.

[0257] When the polyamide layer of the obtained multilayer container contains the polyester resin (Z), as a method for mixing the masterbatch with the remaining polyamide resin (Y) and the remaining polyester resin (Z), dry blending and further kneading can be mentioned, and dry blending is preferred. In dry blending, it is preferred that pellets of the masterbatch, pellets of the remaining polyamide resin (Y) and pellets of the remaining polyester resin (Z) are mixed with a mixing device such as a tumble mixer.

[0258] The total mixing method is a method of kneading and mixing the total amount of the polyamide resin (Y) used in the polyamide layer with the yellowing inhibitor (A) and the oxidation accelerator (B).

[0259] When the polyamide layer of the obtained multilayer container contains the polyester resin (Z), the total amount of the polyamide resin (Y), the total amount of the polyester resin (Z), the yellowing inhibitor (A) and the oxidation accelerator (B) used in the polyamide layer are kneaded and mixed.

[0260] From the viewpoint of sufficient mixing, the kneading temperature is preferably 245 to 300° C., more preferably 250 to 290° C., and further preferably 255 to 280° C. From the viewpoint of sufficient mixing, the kneading time is preferably 10 to 600 seconds, more preferably 20 to 400 seconds, and further preferably 30 to 300 seconds. As the apparatus used in kneading, an open type stirring roll, a non-open type Banbury mixer, a kneader, a continuous kneading machine (single screw kneading machine, twin screw kneading machine, multi-screw kneading machine, etc.) and the like can be cited.

[0261] The composition of the polyamide resin mixture obtained in this step is preferably the same as that of the above-mentioned <polyamide layer>.

[0262] <Step 2 (Step of Obtaining a Multilayer Preform)>

[0263] In step 2, the polyamide resin mixture and the polyester resin composition containing the polyester resin (X) are co-injection molded to obtain a multilayer preform.

[0264] The polyester resin composition preferably has the same composition as that of the <polyester layer>.

[0265] In co-injection molding, a mixture of polyester resin and polyamide resin is extruded from a mold separately and co-injection molded to form a multi-layer preform.

[0266] <Step 3 (blow molding step)>

[0267] In step 3, the multi-layer preform is blow-molded.

[0268] In the method for producing a multi-layer container of the present invention, the multi-layer preform (multi-layer parison) obtained in step 2 is preferably molded by stretch blow molding.

[0269] Among them, in step 2, the multilayer preform obtained by coinjection molding is preferably subjected to stretch blow molding, and the multilayer preform obtained by coinjection molding is more preferably subjected to biaxial stretch blow molding. It should be noted that as conditions for biaxial stretch blow molding, it is preferred that the preform heating temperature is 95 to 110° C., the primary blow molding pressure is 0.5 to 1.2 MPa, and the secondary blow molding pressure is 2.0 to 2.6 MPa, thereby suppressing the occurrence of uneven thickness and uneven stretching, and a multilayer container with excellent strength can be obtained.

[0270] [Method for producing recycled polyester]

[0271] The multi-layer container of the present invention is suitable for recycling as described above, and the multi-layer container of the present invention can be used as a raw material to produce recycled polyester.

[0272] The method for producing the regenerated polyester of the present invention preferably comprises a step of recovering the polyester from the multi-layer container.

[0273] That is, it is preferred to have a step of recovering polyester from a multi-layer container, wherein the multi-layer container comprises: a polyester layer comprising a polyester resin (X); and a polyamide layer comprising a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B), wherein the content of the polyamide resin (Y) is 0.05 to 7.0% by mass relative to the total amount of all the polyamide layers and all the polyester layers, and the yellowing inhibitor (A) is a dye, and the content of the yellowing inhibitor (A) is 1 to 30 ppm relative to the total amount of all the polyamide layers and all the polyester layers.

[0274] The method for producing recycled polyester from a multi-layer container preferably comprises removing all or part of the polyamide layer from the multi-layer container, recovering the polyester constituting the polyester layer, and using the recycled polyester as the recycled polyester. It should be noted that the method for producing recycled polyester from a multi-layer container is not limited to the above method, and may be a method for producing recycled polyester without removing the polyamide resin.

[0275] The regenerated polyester obtained by the present production method can be used for various purposes such as resin molded products and fibers.

[0276] Hereinafter, the method for producing the regenerated polyester of the present invention will be described in detail.

[0277] In the present production method, the multilayer container is usually a used container, but may be an unused container. As the used multilayer container, there can be mentioned those temporarily circulated in the recycling market.

[0278] In the present production method, first, when a cover is attached to the multi-layer container, it is preferred that the cover is removed from the multi-layer container.

[0279] Then, the container is pulverized, washed as necessary, and the polyester is selectively taken out and separated as necessary to be recovered as recycled polyester (recovery step).

[0280] Then, the mixture is granulated as necessary to form pellets (granulation step).

[0281] Furthermore, a crystallization step and a solid phase polymerization step (crystallization / solid phase polymerization step) are performed as necessary.

[0282] Each step is described below.

[0283] <Recycling Process>

[0284] The recycling step is a step of crushing the multilayer container and recovering the recycled polyester.

[0285] Among them, it is preferred to pulverize the multilayer container, remove all or part of the polyamide layer, and selectively extract the polyester, and it is more preferred to classify the polyester and the polyamide resin constituting the polyamide layer.

[0286] The multi-layer container can be crushed using a single screw crusher, a twin screw crusher, a triple screw crusher, a shredder or the like. The crushed product obtained by crushing is in the form of flakes, powder or blocks, for example. However, since the main body of the multi-layer container and other parts thereof are mostly thin and thick multi-layer stacked structures with a thickness of less than several mm, most of the crushed product is usually in the form of flakes. It should be noted that the flake-like crushed product refers to a flake or flat product with a thickness of less than about 2 mm.

[0287] In addition, in the multilayer container, the polyester layer and the polyamide layer are structurally integrated, but they are usually not bonded to each other, and the polyester and polyamide resins are easily separated as independent pulverized products during the pulverization process. In addition, by making them into flakes, they can be easily separated by being rolled up by the air flow of the air separation described later.

[0288] However, polyester and polyamide resin may not be completely separated in the pulverization process, and the pulverized product is separated into a product with a relatively high polyester content and a product with a relatively low polyester content and a relatively high polyamide resin content. It should be noted that, hereinafter, for the sake of convenience, the product with a relatively high polyester content is referred to as polyester, and the product with a relatively high polyamide resin content is referred to as polyamide resin.

[0289] As described above, the pulverized product is classified into polyester and polyamide resins (classification step).

[0290] As the classification method, specific gravity screening using the difference in specific gravity between polyester and polyamide resins is preferably used.

[0291] That is, it is preferred that the polyamide layer be removed by pulverizing the multilayer container and then separating by air separation.

[0292] As specific gravity screening, specifically, there can be cited wind separation that uses wind power to screen the pulverized material. For example, the wind separation method can be as follows: in a separation device that can generate a swirling airflow inside, the pulverized material that contacts the airflow generated by the separation device is classified into those with a large specific gravity or a small specific surface area that naturally fall due to their own weight; and those with a small specific gravity or a large specific surface area that are rolled up by the airflow and recovered.

[0293] In this method, the ground polyester naturally falls due to its own weight, while the ground polyamide resin is rolled up, so that the polyester and the polyamide resin can be classified and recovered.

[0294] In this air separation, the same operation can be repeated for the same pulverized material. For example, the naturally fallen material can be further air separated to increase the polyester content in the recycled polyester.

[0295] It should be noted that the classification method is not limited to air separation, and the following methods can be cited: a method in which the pulverized material is immersed in a liquid such as water and classified according to the difference in specific gravity of the pulverized material relative to the liquid; a method in which constant vibration is applied to the pulverized material, pulverized materials with different specific gravities are separated and classified; etc.

[0296] <Granulation process>

[0297] The recycled polyester after recovery is preferably granulated into pellets in order to facilitate handling during molding and the like.

[0298] Granulation can be performed before or after the crystallization / solid phase polymerization step described below, but is preferably performed before the crystallization / solid phase polymerization step. Performing granulation before the crystallization / solid phase polymerization step improves operability in the crystallization / solid phase polymerization step.

[0299] In the granulation process, the crushed material is preferably plasticized and granulated by melt blending. As the granulating device for plasticization and granulation, single screw extruder, twin screw extruder, multi-screw extruder, etc. can be cited, but any device can be used as long as it is a known device. As the shape of the pellets, cylindrical, spherical, elliptical spherical are preferred.

[0300] Granulation is preferably performed, for example, by extruding the plasticized recycled polyester into strands, cooling them in a water tank, and cutting them in a granulator to form pellets. The pellets taken out of the water tank are usually dried to remove moisture adhering to the surface.

[0301] <Crystallization / Solid Phase Polymerization Step>

[0302] After the polyester recovery step, preferably at least one step selected from a crystallization step and a solid phase polymerization step is performed, and more preferably both the crystallization step and the solid phase polymerization step are performed. The crystallization / solid phase polymerization step is preferably performed on the pelletized polyester, but may also be performed on a non-pelletized polyester (e.g., a pulverized product).

[0303] In addition, when both crystallization and solid phase polymerization are performed, it is preferable to perform solid phase polymerization after crystallizing the polyester.

[0304] The crystallization of the polyester is carried out by keeping the polyester under a certain heating condition. The crystallization is preferably carried out by heating the polyester at, for example, 100 to 230° C. The polyester is crystallized to prevent the polyesters from fusing to each other or adhering to the inner surface of the device during solid phase polymerization or molding.

[0305] Solid phase polymerization is preferably carried out by maintaining the temperature at a temperature of (melting point of polyester - 80°C) or higher and lower than the melting point of polyester for a certain period of time. By setting the temperature lower than the melting point, the polyester is prevented from melting, for example, the polyester is prevented from adhering to the surface of the device and reducing the working efficiency. In addition, by setting the temperature higher than (melting point - 80°C), the polymerization is carried out at a sufficient polymerization rate, and it becomes easy to obtain the desired physical properties.

[0306] Solid phase polymerization can be implemented under vacuum or under an inert gas stream such as nitrogen or argon. When implemented under vacuum, it is preferably 1.0 torr or less, more preferably 0.5 torr or less, and further preferably 0.1 torr or less. In addition, under vacuum or under an inert gas stream such as nitrogen or argon, it is preferred to reduce the residual oxygen concentration in the system as much as possible, and the oxygen concentration is preferably 300 ppm or less, more preferably 30 ppm or less. The oxygen concentration is set to 30 ppm or less, thereby becoming less likely to cause poor appearance such as yellowing.

[0307] When solid phase polymerization is carried out under vacuum, it is preferred to frequently repeat stirring or mixing of the polyester while uniformly conducting heat. When carried out in the presence of an inert gas, it is preferred to frequently keep the surface of the polyester in contact with the dried gas under a flow of the dried gas.

[0308] The solid phase polymerization apparatus used for the crystallization / solid phase polymerization step can include: a drum-type intermittent apparatus equipped with a heating jacket, a drying silo type equipped with an inert gas flow device, a crystallization apparatus and a reactor equipped with stirring blades and a discharge screw inside, etc. It should be noted that crystallization and solid phase polymerization are preferably carried out continuously or simultaneously in the same apparatus.

[0309] The heating time for solid phase polymerization is appropriately determined depending on the apparatus and other conditions, but may be a time for obtaining sufficient physical properties of the polyester.

[0310] Solid phase polymerization keeps the polyester at high temperature for a long time, so if there are impurities in the polyester, the quality of the color tone may be deteriorated. In the above removal step, it is preferred that most of the polyamide resin is removed. In this case, the quality deterioration that may occur during solid phase polymerization is suppressed to a minimum.

[0311] In the method for producing regenerated polyester of the present invention, steps other than the steps described above may be performed, and a washing step may be performed to remove the contents adhering to the inside of the multilayer container. The washing is preferably performed by rinsing with a liquid, washing with water, washing with an alkaline aqueous solution, or both.

[0312] In addition, the cleaning can be performed before the multilayer container is pulverized into a pulverized product, or after the pulverization, and is preferably performed before any of granulation, crystallization, and solid phase polymerization. Furthermore, the cleaning step can be performed simultaneously with the pulverization step in a pulverizer that performs cleaning and pulverization at the same time, which is called a wet pulverizer.

[0313] In addition, when the washing step is performed, a drying step may be performed after the washing step. By performing the drying step, the moisture content of the regenerated polyester obtained by the present method can be reduced, so that high-quality regenerated polyester with high thermal stability can be provided. The drying step can be performed, for example, using air supply or hot air from a dryer.

[0314] When the method for producing recycled polyester includes a step of removing the polyamide resin, the content of the polyamide resin in the obtained recycled polyester is preferably less than 1% by mass, more preferably less than 0.8% by mass, and further preferably less than 0.6% by mass. In this way, the content of the polyamide resin is reduced, and the quality of the recycled polyester becomes good.

[0315] Example

[0316] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0317] [raw material]

[0318] The polyester resin, yellowing inhibitor, oxidation accelerator, and greening inhibitor used in the examples and comparative examples are as follows. The polyamide resin used was the one produced in the following Production Example 1.

[0319] <Polyester resin (X1)>

[0320] Isophthalic acid copolymer polyethylene terephthalate (intrinsic viscosity: 0.83 dL / g, melting point: 248°C, isophthalic acid modification rate: 1.5 mol% (in dicarboxylic acid unit)), trade name: BK2180, manufactured by Mitsubishi Chemical Corporation

[0321] <Yellowing Inhibitor>

[0322] Blue RR: Solvent Blue 97 (anthraquinone dye), trade name: MACROLEX Blue RR Gran, manufactured by LANXESS,

[0323] K6907: Pigment Blue 15:1 (α-type copper phthalocyanine pigment), trade name: HELIOGEN BLUE K6907, manufactured by BASF, form: powder

[0324] <Oxidation Accelerator>

[0325] Cobalt(II) stearate: manufactured by Tokyo Chemical Industry Co., Ltd.

[0326] Cobalt(II) neodecanoate: manufactured by Nippon Chemical Industry Co., Ltd.

[0327] <Greening Inhibitor>

[0328] Violet 3R: Solvent Violet 36 (anthraquinone dye), trade name: MACROLEX Violet 3R Ran, manufactured by LANXESS

[0329] K4535: Pigment Red 202 (quinacridone pigment), trade name: Cinquasia Magenta K4535, manufactured by BASF

[0330] <Polyester resin (Z1)>

[0331] Isophthalic acid copolymer polyethylene terephthalate (intrinsic viscosity: 0.83 dL / g, melting point: 248°C), trade name: BK2180, manufactured by Mitsubishi Chemical Corporation

[0332] <Polyamide resin (Y1)>

[0333] Production Example 1 (Production of polyamide resin (Y1))

[0334] In a 50-liter reaction vessel equipped with a stirrer, a partial condenser, a full condenser, a thermometer, a dropping funnel, a nitrogen inlet pipe, and a strand die, 15000 g (102.6 mol) of adipic acid, 13.06 g (123.3 mmol, 151 ppm based on the phosphorus atom concentration in the polyamide) of sodium hypophosphite monohydrate (NaH2PO2·H2O), and 6.849 g (83.49 mmol, 0.68 in terms of the molar ratio to sodium hypophosphite monohydrate) of a precise weight were placed, and nitrogen replacement was performed thoroughly. Then, the system was heated to 170° C. while stirring in a small amount of nitrogen gas flow. 13896 g (102.0 mol, 0.994 in terms of the input molar ratio) of m-xylylenediamine was added dropwise thereto while stirring, and the generated condensation water was discharged to the outside of the system while the system was continuously heated. After the dropwise addition of meta-xylylenediamine was completed, the internal temperature was set to 260° C. and the reaction was continued for 40 minutes. Then, the system was pressurized with nitrogen, and the polymer was taken out from the strand die and pelletized to obtain about 24 kg of polyamide.

[0335] Then, the polyamide is added to a jacketed drum dryer equipped with a nitrogen inlet pipe, a vacuum line, a vacuum pump, and a thermocouple for measuring the internal temperature. While rotating the drum dryer at a constant speed, the inside of the drum dryer is fully replaced with nitrogen having a purity of 99% by volume or more. Then, the drum dryer is heated under the same nitrogen flow, and the pellet temperature is raised to 150°C in about 150 minutes. When the pellet temperature reaches 150°C, the pressure in the system is reduced to less than 1 torr. The temperature is further continued to rise, and after raising the pellet temperature to 200°C in about 70 minutes, it is maintained at 200°C for 30 to 45 minutes. Then, nitrogen having a purity of 99% by volume or more is introduced into the system, and the drum dryer is kept rotating and cooled to obtain a polyamide resin (Y1).

[0336] [evaluate]

[0337] The multi-layered container of the present invention was evaluated by the following method.

[0338] <Oxygen Permeability (Evaluation of Oxygen Barrier Properties)>

[0339] The oxygen permeability was evaluated by the following method.

[0340] Evaluated according to the oxygen permeability test based on the MOCON method in accordance with ASTM D3985. OX-TRAN2 / 61 manufactured by MOCON was used for the measurement. 100 mL of water was filled into a 500 mL bottle obtained in each embodiment and comparative example, and 1 atm of nitrogen was circulated in the bottle at 20 mL / min under the conditions of an oxygen partial pressure of 0.21 atm, a temperature of 23°C, a humidity of 100% RH inside the bottle, and an external humidity of 50% RH. The oxygen contained in the nitrogen after circulation inside the container was detected by a coulometric sensor for measurement. The lower limit of measurement was set to 0.001 cc / (bottle·day·0.21 atm).

[0341] The oxygen permeability is determined based on the oxygen permeability value after 7 days from the start of the measurement. The smaller the oxygen permeability value, the better the oxygen barrier property.

[0342] <Yellowness Δb* (Evaluation of yellowing inhibition ability)>

[0343] Yellowness Δb of the recycled polyester pellets obtained in [Production of Recycled Polyester] described below * The results were measured by the following method and evaluated based on the following criteria.

[0344] The color tone of the pellets was measured as follows: Based on JIS Z 8722, a 30 mmφ cuvette container was filled with pellets using a colorimeter ZE-2000 (manufactured by Nippon Denshoku Industries, 12V 20W halogen lamp light source) and the color tone was measured as the average value of four measurements by a reflection method.

[0345] It should be noted that b * Value indicates chromaticity. +b * Indicates yellow direction, -b * Indicates the blue direction. In addition, Δb * The smaller the absolute value of the value, the more the yellowing is suppressed. In addition, it means that the colorlessness is high. * The values ​​represent the b values ​​of the samples of the following examples and comparative examples. * The values ​​are the same as those of the polyester resin alone subjected to the same treatment as in the examples and comparative examples. * The difference in value.

[0346] <Greenness Δa * >

[0347] The greenness Δa of the recycled polyester pellets obtained in the [Manufacturing of Recycled Polyester] described below * The results were measured by the following method and evaluated based on the following criteria.

[0348] The color tone of the pellets was measured as follows: Based on JIS Z 8722, a 30 mmφ cuvette container was filled with pellets using a colorimeter ZE-2000 (manufactured by Nippon Denshoku Industries, 12V 20W halogen lamp light source) and the color tone was measured as the average value of four measurements by a reflection method.

[0349] It should be noted that a * The value indicates the chromaticity. * Indicates red direction, -a * Indicates the green direction. In addition, Δa * The smaller the absolute value of the value, the more the green shift is suppressed. In addition, it means that the achromaticity is high. * The values ​​represent the a values ​​of the samples of the following examples and comparative examples. * The values ​​are the same as those of the polyester resin alone subjected to the same treatment as in the examples and comparative examples. * The difference in value.

[0350] [Manufacturing of polyamide resin mixture by masterbatch method]

[0351] Production Example 2

[0352] 95.35 mass% of polyamide resin (Y1), 0.20 mass% of BlueRR as a yellowing inhibitor, 4.25 mass% of cobalt (II) stearate as an oxidation accelerator, and 0.20 mass% of Violet3R as a greening inhibitor were pre-dry mixed. Then, the dry mixed mixture was melt-kneaded at 260°C using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain master batch pellets. Then, the pellets were dried in a vacuum dryer at 150°C for 5 hours to obtain master batch A.

[0353] Next, the obtained master batch A and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 1 (master batch A / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0354] Production Example 3

[0355] 94.95 mass% of polyamide resin (Y1), 0.40 mass% of BlueRR as a yellowing inhibitor, 4.25 mass% of cobalt (II) stearate as an oxidation promoter, and 0.40 mass% of Violet3R as a greening inhibitor were pre-dry mixed. Then, the dry mixed mixture was melt-kneaded at 260°C using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain master batch pellets. Then, the pellets were dried in a vacuum dryer at 150°C for 5 hours to obtain master batch B.

[0356] Next, the obtained master batch B and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 1 (master batch B / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0357] Production Example 4

[0358] 96.48 mass % of polyamide resin (Y1), 0.40 mass % of BlueRR as a yellowing inhibitor, 2.72 mass % of cobalt (II) neodecanoate as an oxidation accelerator, and 0.40 mass % of Violet3R as a greening inhibitor were pre-dry mixed. Then, the dry mixed mixture was melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain master batch pellets. Then, the pellets were dried in a vacuum dryer at 150° C. for 5 hours to obtain a master batch C.

[0359] Next, the obtained master batch C and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 1 (master batch C / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0360] Production Example 5

[0361] 97.08 mass % of polyamide resin (Y1), 0.40 mass % of BlueRR as a yellowing inhibitor, 2.12 mass % of cobalt stearate (II) as an oxidation promoter, and 0.40 mass % of Violet3R as a greening inhibitor were pre-dry mixed. Then, the dry mixed mixture was melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain master batch pellets. Then, the pellets were dried in a vacuum dryer at 150° C. for 5 hours to obtain a master batch D.

[0362] Next, the obtained master batch D and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 1 (master batch D / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0363] Production Example 6

[0364] 95.35 mass % of polyamide resin (Y1), 0.40 mass % of BlueRR as a yellowing inhibitor, and 4.25 mass % of cobalt stearate (II) as an oxidation accelerator were pre-dry blended. No greening inhibitor was added in the dry blending. Then, the dry blended mixture was melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain masterbatch pellets. Then, the pellets were dried in a vacuum dryer at 150° C. for 5 hours to obtain masterbatch E.

[0365] Next, the obtained master batch E and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 1 (master batch E / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0366] Production Example 7

[0367] 94.95 mass% of polyester resin (X1), 0.40 mass% of BlueRR as a yellowing inhibitor, 4.25 mass% of cobalt stearate (II) as an oxidation accelerator, and 0.40 mass% of Violet3R as a greening inhibitor were preliminarily dry-blended. Then, the dry-blended mixture was melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain masterbatch pellets. Then, the pellets were dried in a vacuum dryer at 150° C. for 5 hours to obtain a masterbatch F.

[0368] Next, the obtained master batch F and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 1 (master batch F / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0369] Production Example 8

[0370] 93.75 mass % of polyamide resin (Y1), 0.40 mass % of K6907 as a yellowing inhibitor pigment, 4.25 mass % of cobalt stearate (II) as an oxidation accelerator, and 1.60 mass % of K4535 as a greening inhibitor pigment were preliminarily dry-blended. Then, the dry-blended mixture was melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain masterbatch pellets. Then, the pellets were dried in a vacuum dryer at 150° C. for 5 hours to obtain a masterbatch G.

[0371] Next, the obtained master batch G and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 1 (master batch G / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0372] Production Example 9

[0373] 95.75 mass % of polyamide resin (Y1) and 4.25 mass % of cobalt (II) stearate as an oxidation accelerator were preliminarily dry-blended. The dry-blended mixture was then melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain masterbatch pellets. The pellets were then dried in a vacuum dryer at 150° C. for 5 hours to obtain a masterbatch H.

[0374] Next, the obtained master batch H and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 1 (master batch H / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0375] [Manufacturing of polyamide resin mixture containing polyester resin]

[0376] Production Example 10 (Polyamide resin composition (Y2))

[0377] 99.2 mass % of polyamide resin (Y1), 0.4 mass % of BlueRR as a yellowing inhibitor, and 0.4 mass % of Violet3R as a greening inhibitor were preliminarily dry-blended. Next, the dry-blended mixture was melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain masterbatch pellets. The pellets were then dried in a vacuum dryer at 150° C. for 5 hours to obtain a polyamide resin composition (Y2).

[0378] Production Example 11 (Polyester resin composition (Z2))

[0379] 95.75 mass % of polyester resin (Z1) and 4.25 mass % of cobalt (II) stearate as an oxidation accelerator were preliminarily dry-blended. The dry-blended mixture was then melt-kneaded at 280° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain masterbatch pellets. The pellets were then dried in a vacuum dryer at 150° C. for 5 hours to obtain a polyamide resin composition (Z2).

[0380] Production Examples 12 to 18 (Polyamide resin mixture containing polyester resin)

[0381] A polyamide resin mixture was prepared by mixing a polyamide resin (Y1), a polyamide resin composition (Y2), a polyester resin (Z1) and a polyester resin composition (Z2) at the mass ratio shown in Table 2. In Table 2, each polyamide resin mixture is indicated by a production example number.

[0382] [Manufacture of multi-layer containers]

[0383] Examples 1 to 13 and Comparative Examples 1 to 4

[0384] <Preform Forming>

[0385] An injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., model DU130CI) with two injection barrels and a two-piece mold (manufactured by Kortec) was used. Polyester resin (X1) was injected from one injection barrel, and the polyamide resin mixture obtained in Manufacturing Examples 2 to 18 was injected from the other injection barrel. Under the conditions shown below, a three-layer preform (set to be equivalent to 25g per preform) consisting of polyester layer / polyamide layer / polyester layer was injection molded in such a way that the mass of the polyamide layer relative to the entire preform became the amount described in Tables 1 and 2 and was manufactured. The shape of the preform is as follows: total length 95mm, outer diameter 22mm, wall thickness 4.0mm. The molding conditions of the three-layer preform are shown below.

[0386]

[0387] <Bottle molding>

[0388] The preform obtained above was subjected to biaxial stretch blow molding using a blow molding device (EFB1000ET, manufactured by Frontier) to obtain a bottle (hollow multilayer container). The bottle had a total length of 223 mm, an outer diameter of 65 mm, an internal volume of 500 mL, and a petal-shaped bottom. No shallow concave portion was provided in the main body. The biaxial stretch blow molding conditions were as follows.

[0389] The oxygen permeability was evaluated using the bottles obtained in Examples 1 to 7 and Comparative Examples 1 and 2. The results are shown in Table 1.

[0390] Preform heating temperature: 103℃

[0391] Stretching rod pressure: 0.7MPa

[0392] One blow molding pressure: 1.1MPa

[0393] Secondary blow molding pressure: 2.5MPa

[0394] One blow molding delay time: 0.30 seconds

[0395] Blowing time: 0.30 seconds

[0396] Second blow molding time: 2.0 seconds

[0397] Blow molding exhaust time: 0.6 seconds

[0398] Mold temperature: 30℃

[0399] [Manufacturing of recycled polyester]

[0400] <Recovery / Pelletization Process>

[0401] 10 kg of the hollow multilayer containers obtained in Examples 1 to 13 and Comparative Examples 1 to 4 were pulverized with a pulverizer having a mesh diameter of 8 mm, and the obtained flaky pulverized products were recovered as recycled polyester.

[0402] The recovered recycled polyester was extruded in a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) at a heater temperature of 270° C. and a discharge rate of 20 kg / hour to form strands, which were then cut in a pelletizer while being cooled in a water tank to form pellets. It should be noted that in Examples 1 to 13 and Comparative Examples 1 to 4, air separation of the polyamide layer was not performed.

[0403] <Crystallization / Solid Phase Polymerization Step>

[0404] The pellets obtained in the above granulation step were heated at 200°C for 7 hours under a vacuum reduced to less than 1 torr. The pellets after the heat treatment were taken out and the yellowness Δb * and greenness Δa * The results are shown in Tables 1 and 2.

[0405] [Table 1]

[0406] Table 1

[0407]

[0408] As shown in Table 1, the multilayer container of the example is excellent in oxygen barrier property, and yellowing of the recycled polyester during recycling can be suppressed even when a small amount of yellowing inhibitor is used.

[0409] [Table 2]

[0410] Table 2

[0411]

[0412] As shown in Table 2, in the multi-layer container of the example, when the polyamide layer contains a polyester resin, yellowing of the recycled polyester during recycling can be suppressed even with the use of a small amount of a yellowing inhibitor.

[0413] [Manufacture of polyamide resin mixture or polyester resin mixture]

[0414] Production Example 19 (Production of polyamide resin mixture)

[0415] 94.95 mass% of polyamide resin (Y1), 0.40 mass% of BlueRR as a yellowing inhibitor, 4.25 mass% of cobalt stearate (II) as an oxidation accelerator, and 0.40 mass% of Violet3R as a greening inhibitor were pre-dry mixed. Then, the dry mixed mixture was melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain master batch pellets. Then, the pellets were dried in a vacuum dryer at 150° C. for 5 hours to obtain master batch I.

[0416] Next, the obtained master batch I and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 3 (master batch I / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0417] Production Example 20 (Production of polyamide resin mixture)

[0418] 95.75 mass % of polyamide resin (Y1) and 4.25 mass % of cobalt (II) stearate as an oxidation accelerator were preliminarily dry-blended. The dry-blended mixture was then melt-kneaded at 260° C. using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain masterbatch pellets. The pellets were then dried in a vacuum dryer at 150° C. for 5 hours to obtain a masterbatch J.

[0419] Next, the obtained master batch J and the remaining amount of the polyamide resin (Y1) were mixed at a mass ratio shown in Table 3 (master batch J / remaining amount of the polyamide resin=10 / 90) to prepare a polyamide resin mixture.

[0420] Production Example 21 (Production of Polyester Resin Mixture)

[0421] 97.60 mass% of polyester resin (X1), 1.20 mass% of BlueRR as a yellowing inhibitor, and 1.20 mass% of Violet3R as a greening inhibitor were pre-dry blended. The dry blended mixture was then melt-kneaded at 260°C using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) to obtain masterbatch pellets. The pellets were then dried in a vacuum dryer at 150°C for 5 hours to obtain a masterbatch K.

[0422] Next, the obtained master batch K and the remaining amount of the polyester resin (X1) were mixed at a mass ratio shown in Table 3 (master batch K / remaining amount of the polyester resin=5 / 95) to prepare a polyester resin mixture.

[0423] [Manufacture of multi-layer containers]

[0424] Example 14 and Comparative Example 5

[0425] <Preform Forming>

[0426] An injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., model DU130CI) with two injection barrels and a two-piece mold (manufactured by Kortec) was used. The polyester resin (X1) (Example 14) or the polyester resin mixture obtained in Preparation Example 21 (Comparative Example 5) was injected from one injection barrel, and the polyamide resin mixture obtained in Preparation Example 19 (Example 14) or the polyamide resin mixture obtained in Preparation Example 20 (Comparative Example 5) was injected from another injection barrel. Under the conditions shown below, a three-layer preform (set to be equivalent to 25 g per preform) formed of polyester layer / polyamide layer / polyester layer was injection molded in such a way that the mass of the polyamide layer relative to the entire preform was as described in Table 3. The shape of the preform is as follows: total length 95 mm, outer diameter 22 mm, wall thickness 4.0 mm. The molding conditions of the three-layer preform are shown below.

[0427]

[0428]

[0429] <Bottle molding>

[0430] The preform obtained above was subjected to biaxial stretch blow molding using a blow molding device (EFB1000ET, manufactured by Frontier) to obtain a bottle (hollow multilayer container). The bottle had a total length of 223 mm, an outer diameter of 65 mm, an internal volume of 500 mL, and a petal-shaped bottom. No shallow concave portion was provided in the main body. The biaxial stretch blow molding conditions were as follows.

[0431] Preform heating temperature: 103℃

[0432] Stretching rod pressure: 0.7MPa

[0433] One blow molding pressure: 1.1MPa

[0434] Secondary blow molding pressure: 2.5MPa

[0435] One blow molding delay time: 0.30 seconds

[0436] Blowing time: 0.30 seconds

[0437] Second blow molding time: 2.0 seconds

[0438] Blow molding exhaust time: 0.6 seconds

[0439] Mold temperature: 30℃

[0440] [Manufacturing of recycled polyester including air separation and classification process]

[0441] <Recovery / Wind Classification / Pelletization Process>

[0442] 10 kg of the hollow multilayer containers obtained in the above-mentioned Example 14 and Comparative Example 5 were crushed in a crusher with a mesh diameter of 8 mm to form flakes, and then the flakes were washed with water. Then, using Floss separator CFS-150 (manufactured by ACO Co., Ltd.), the material with a heavy specific gravity that fell to the bottom layer was recovered at a supply speed of 10 kg / hour, a suction fan of 35 Hz, and a secondary blower of 30 Hz. Finally, the flake-shaped crushed material that fell to the bottom layer was recovered as recycled polyester.

[0443] The recovered recycled polyester was extruded using a twin-screw extruder (TEM26SX manufactured by Toshiba Machine Co., Ltd.) at a heater temperature of 270° C. and a discharge rate of 20 kg / hour to form strands, which were then cut in a pelletizer to pelletize while being cooled in a water tank.

[0444] <Crystallization / Solid Phase Polymerization Step>

[0445] The pellets obtained in the above granulation step were heated at 200°C for 7 hours under a vacuum reduced to 1 torr or less. The pellets after the heat treatment were taken out and evaluated for yellowness Δb* and greenness Δa*. The results are shown in Table 3.

[0446] [Table 3]

[0447] Table 3

[0448]

[0449] As shown in Table 3, the multilayer container of Example 14 can suppress yellowing of the recycled polyester even when the polyamide layer is removed during recycling by adding a small amount of yellowing inhibitor to the polyamide layer. The multilayer container of Comparative Example 5 can suppress yellowing of the recycled polyester even when the polyamide layer is removed during recycling by adding a yellowing inhibitor to the polyester layer, which disrupts the balance between the amount of polyamide resin and the yellowing inhibitor contained in the recycled polyester and increases the Δb* value.

Claims

1. A multi-layer container, comprising: a polyester layer comprising a polyester resin (X); and A polyamide layer comprising a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B), The content of the polyamide resin (Y) is 0.05 to 7.0% by mass based on the total amount of the polyamide layer and the polyester layer. Yellowing inhibitor (A) is a dye, The content of the yellowing inhibitor (A) in the polyamide layer is 0.005 to 1.0% by mass. The content of the yellowing inhibitor (A) is 1.5 to 30 ppm based on the total amount of all polyamide layers and all polyester layers.

2. The multi-layer container according to claim 1, wherein The polyester resin (X) has a dicarboxylic acid-derived structural unit containing 80 mol % or more of a terephthalic acid-derived structural unit and a diol-derived structural unit containing 80 mol % or more of an ethylene glycol-derived structural unit.

3. The multi-layer container according to claim 1 or 2, wherein: The polyamide resin (Y) has a diamine-derived structural unit containing 80 mol % or more of a xylylenediamine-derived structural unit and a dicarboxylic acid-derived structural unit containing 80 mol % or more of adipic acid-derived structural unit.

4. The multi-layer container according to claim 1 or 2, wherein: The oxidation accelerator (B) is a compound containing a transition metal.

5. The multi-layer container according to claim 4, wherein: The transition metal is at least one selected from the group consisting of cobalt, iron, manganese, and nickel.

6. The multi-layer container according to claim 1 or 2, wherein: The yellowing inhibitor (A) is an anthraquinone dye.

7. The multi-layer container according to claim 1 or 2, wherein: The polyamide layer further comprises a greening inhibitor (C).

8. The multi-layer container according to claim 7, wherein: The greening inhibitor (C) is at least one selected from the group consisting of anthraquinone dyes and azo dyes.

9. The multi-layer container according to claim 1 or 2, wherein: The polyamide layer further comprises a polyester resin (Z).

10. The multi-layer container according to claim 9, wherein The content of the polyester resin (Z) in the polyamide layer is 5 to 70% by mass.

11. The multi-layer container according to claim 1 or 2, wherein: The multi-layer container is a multi-layer hollow container.

12. The multi-layer container according to claim 1 or 2, wherein: The multi-layer container has a 2-5 layer structure, and the outermost layer is a polyester layer.

13. The multi-layer container according to claim 1 or 2, wherein: The multi-layer container has a 3-5 layer structure, and the outermost layer and the innermost layer are polyester layers.

14. A method for manufacturing a multi-layer container, wherein: The multi-layer container has: a polyester layer comprising a polyester resin (X); and A polyamide layer comprising a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B), The content of the polyamide resin (Y) is 0.05 to 7.0% by mass based on the total amount of the polyamide layer and the polyester layer. Yellowing inhibitor (A) is a dye, The content of the yellowing inhibitor (A) in the polyamide layer is 0.005 to 1.0% by mass. The content of the yellowing inhibitor (A) is 1.5 to 30 ppm based on the total amount of the polyamide layer and the polyester layer. The manufacturing method comprises the following steps: Step 1, mixing a polyamide resin (Y), a yellowing inhibitor (A) and an oxidation accelerator (B) to prepare a polyamide resin mixture; Step 2, co-injection molding the polyamide resin mixture and the polyester resin composition containing the polyester resin (X) to obtain a multilayer preform; as well as Step 3, blow molding the multi-layer preform.

15. The method for manufacturing a multi-layer container according to claim 14, wherein: In step 1, a greening inhibitor (C) is further mixed.

16. The method for manufacturing a multi-layer container according to claim 14 or 15, wherein: In step 1, a polyester resin (Z) is further mixed.

17. The method for manufacturing a multi-layer container according to claim 14 or 15, wherein: In step 1, a polyamide resin or a polyester resin, a yellowing inhibitor (A) and an oxidation accelerator (B) are kneaded and then mixed with a polyamide resin (Y).

18. The method for manufacturing a multi-layer container according to claim 14 or 15, wherein: The oxidation accelerator (B) is a compound containing a transition metal.

19. The method for manufacturing a multi-layer container according to claim 18, wherein: The transition metal is at least one selected from the group consisting of cobalt, iron, manganese, and nickel.

20. The method for manufacturing a multi-layer container according to claim 14 or 15, wherein: The yellowing inhibitor (A) is an anthraquinone dye.

21. The method for manufacturing a multi-layer container according to claim 15, wherein: The greening inhibitor (C) is at least one selected from the group consisting of anthraquinone dyes and azo dyes.

22. A method for producing recycled polyester, comprising the step of recovering polyester from the multilayer container according to any one of claims 1 to 13. 23 . The method for producing regenerated polyester according to claim 22 , comprising the step of removing all or part of the polyamide layer from the multi-layer container to recover the polyester.

24. The method for producing regenerated polyester according to claim 22 or 23, wherein: After the multi-layer container is pulverized, the polyamide layer is removed by air separation.

25. The method for producing regenerated polyester according to claim 22 or 23, wherein: After the step of recovering the polyester, one or more steps selected from a crystallization step and a solid phase polymerization step are performed.

Citation Information

Patent Citations

  • Multi-layer container and production method therefor, single-layer container production method, and recycled polyester resin production method

    WO2017057463A1

  • Multi-layer bottle

    CN101360601A

  • Synthetic resin bottle

    JP2015024828A